Chemically strengthened lithium disilicate-petalite glass ceramics
By introducing specific stress distribution and controlling Na2O concentration in lithium pyrosilicate-lithium feldspar glass ceramics, the problems of surface vulnerability and blurring of FSM images are solved, and higher chemical durability and damage resistance are achieved.
Patent Information
- Application Number
- CN202411584360.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-11-13
- Filing Date
- 2019-11-12
- Publication Date
- 2025-03-18
AI Technical Summary
The existing lithium pyrosilicate-lithium feldspar glass ceramics form a low-refractive index surface layer rich in sodium during ion exchange, resulting in surface vulnerability to damage and the FSM image becomes blurred, affecting quality control.
By introducing a stress distribution into glass ceramic products, the maximum compression stress is ensured to be 1.8 to 2.2 times the maximum central tension value and the Na2O concentration is controlled to improve chemical durability and damage resistance.
It significantly improves the chemical durability and damage resistance of glass-ceramic products, improves the quality control of the ion exchange process, and avoids surface hazy and damage.
Smart Images

Figure CN119638201A_ABST
Abstract
Description
[0001] This application is a divisional application of a patent application with an application date of November 12, 2019, application number 201980020541.1, and name “Chemically Strengthened Lithium Disilicate-Petalite Glass-Ceramics”.
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application claims priority to and the benefit of U.S. Provisional Application No. 62 / 760,753, filed on November 13, 2018, entitled “Chemically Strengthened Lithium Disilicate-Petalite Glass-Ceramics,” the entire contents of which are incorporated herein by reference. Technical Field
[0004] The present description relates generally to glass articles and, more particularly, to glass-ceramic articles having improved chemical durability and damage resistance and methods of forming the same. Background Art
[0005] When a glass-ceramic having a lithium disilicate crystalline phase undergoes a conventional ion exchange process, a sodium-rich, low refractive index layer is formed on the surface of the glass-ceramic. The presence of this sodium-rich surface layer makes the surface of the glass-ceramic susceptible to subsurface hydration, which can lead to the growth of sodium carbonate crystals on the surface of the glass-ceramic, which in turn can produce surface haziness. The sodium-rich surface layer also exhibits low chemical durability, making the glass-ceramic susceptible to preferential etching, pitting and other surface damage.
[0006] In addition to altering the properties of the glass-ceramic, the presence of the low refractive index layer can blur the images produced during FSM imaging, which makes the use of these images for quality control of the ion exchange process unreliable.
[0007] Therefore, there is a need for glass-ceramic articles having improved chemical durability, improved damage resistance, and methods for improving quality control of ion exchange processes. Summary of the invention
[0008] According to the first aspect disclosed herein, an ion-exchange glass-ceramic article has a thickness t, wherein: the glass article includes stress, and the stress decreases with increasing distance from the outer surface of the ion-exchange glass-ceramic article toward the center line from a depth of about 0.07t to a depth of about 0.26t according to a basically linear function; the stress changes from compressive stress to tensile stress at a depth of about 0.18t to about 0.25t from the outer surface of the ion-exchange glass-ceramic article; and the absolute value of the maximum compressive stress at the outer surface of the ion-exchange glass-ceramic article is 1.8 to 2.2 times the absolute value of the maximum central tension (CT) of the ion-exchange glass-ceramic article; and the fracture toughness of the ion-exchange glass-ceramic article is greater than or equal to 1 MPa√m, which is measured according to the double cantilever beam method.
[0009] According to a second aspect disclosed herein, the ion exchange glass-ceramic product includes the ion exchange glass-ceramic product according to the first aspect, wherein the maximum central tension is greater than or equal to 70 MPa.
[0010] According to a third aspect disclosed herein, the ion exchange glass ceramic product comprises the ion exchange glass ceramic product according to any one of the preceding aspects, wherein the maximum central tension is 80 MPa to 140 MPa.
[0011] According to a fourth aspect disclosed herein, the ion exchange glass ceramic product comprises the ion exchange glass ceramic product according to any one of the preceding aspects, wherein the maximum compressive stress is 180 MPa to 350 MPa.
[0012] According to a fifth aspect disclosed herein, the ion-exchanged glass-ceramic article comprises the ion-exchanged glass-ceramic article according to any one of the preceding aspects, wherein the fracture toughness is 1 MPa√m to 1.5 MPa√m, as measured by a double cantilever beam method.
[0013] According to a sixth aspect disclosed herein, the ion exchange glass-ceramic product comprises the ion exchange glass-ceramic product according to any one of the preceding aspects, wherein the Na2O concentration at the outer surface of the ion exchange glass-ceramic product is less than 10 mol%.
[0014] According to the seventh aspect disclosed herein, an ion exchange glass ceramic article has a thickness t, wherein: the Li ion concentration increases from a surface Li ion concentration to a maximum Li ion concentration as the distance from the outer surface of the ion exchange glass ceramic article increases, wherein the difference between the surface Li ion concentration and the maximum Li ion concentration is less than 5 mol %; the Na ion concentration increases from a surface Na ion concentration and then decreases to a minimum Na ion concentration as the distance from the outer surface of the ion exchange glass ceramic article increases, wherein the difference between the surface Na ion concentration and the minimum Na ion concentration is less than 5 mol %, and the surface Na ion concentration is less than 10 mol %; and the fracture toughness of the ion exchange glass ceramic article is greater than 1 MPa√m, as measured by a double cantilever beam method.
[0015] According to an eighth aspect disclosed herein, the ion exchange glass-ceramic product comprises the ion exchange glass-ceramic product according to the seventh aspect, wherein the Na ion concentration is greater than 0 mol % throughout the thickness t of the ion exchange glass-ceramic product.
[0016] According to a ninth aspect disclosed herein, the ion exchange glass-ceramic product comprises the ion exchange glass-ceramic product according to the seventh or eighth aspect, wherein the Na ion concentration is greater than 0 mol % and less than 2.5 mol %.
[0017] According to a tenth aspect disclosed herein, the ion exchange glass-ceramic product comprises the ion exchange glass-ceramic product according to any one of aspects 7 to 9, wherein the maximum concentration of Li ions is 19 mol % to 32 mol %.
[0018] According to the 11th aspect disclosed herein, the ion exchange glass ceramic article comprises the ion exchange glass ceramic article according to any one of aspects 7 to 10, wherein the fracture toughness is 1 MPa√m to 1.5 MPa√m, as measured by a double cantilever beam method.
[0019] According to a twelfth aspect disclosed herein, the ion exchange glass-ceramic article comprises the ion exchange glass-ceramic article according to any one of aspects 7 to 11, further comprising greater than 0 mol % to 6 mol % of Al 2 O 3 .
[0020] According to a 13th aspect disclosed herein, the ion exchange glass-ceramic product includes the ion exchange glass-ceramic product according to any one of aspects 7 to 12, further comprising 0.7 mol % to 2.2 mol % of P2O5.
[0021] According to a 14th aspect disclosed herein, the ion exchange glass-ceramic product includes the ion exchange glass-ceramic product according to any one of aspects 7 to 13, further comprising 1.7 mol % to 4.5 mol % of ZrO 2 .
[0022] According to a 15th aspect disclosed herein, the ion exchange glass-ceramic product includes the ion exchange glass-ceramic product according to any one of aspects 7 to 14, further comprising 60 mol % to 72 mol % of SiO2.
[0023] According to the 16th aspect disclosed herein, an ion exchange glass ceramic product includes 1% to 30% residual glass content and 70% to 99% crystalline phase, wherein the crystalline phase is selected from lithium pyrosilicate, petalite, β-quartz, β-spodumene solid solution and combinations thereof; the ion exchange glass ceramic product has a thickness t and includes stress, which decreases as the distance from the outer surface of the ion exchange glass ceramic product toward the center line increases, wherein from a depth of about 0.07t to a depth of about 0.26t from the outer surface of the ion exchange glass ceramic product, the stress decreases according to a substantially linear function; the stress transforms from compressive stress to tensile stress at a depth of about 0.18t to about 0.25t from the outer surface of the ion exchange glass ceramic product; and the maximum compressive stress at the outer surface of the ion exchange glass ceramic product is 1.8 to 2.2 times the value of the maximum central tension (CT) of the ion exchange glass product.
[0024] According to the 17th aspect disclosed herein, the ion-exchange glass-ceramic article comprises the ion-exchange glass-ceramic article according to the 16th aspect, wherein the fracture toughness of the ion-exchange glass-ceramic article is 1 MPa√m to 1.5 MPa√m, as measured by a double cantilever beam method.
[0025] According to an eighteenth aspect disclosed herein, the ion-exchange glass-ceramic article comprises the ion-exchange glass-ceramic article according to the sixteenth or seventeenth aspect, wherein the ion-exchange glass-ceramic is opaque.
[0026] According to a 19th aspect disclosed herein, the ion exchange glass-ceramic product comprises the ion exchange glass-ceramic product according to any one of aspects 16 to 18, wherein the maximum compressive stress is 180 MPa to 350 MPa.
[0027] According to the 20th aspect disclosed herein, the ion exchange glass-ceramic article comprises the ion exchange glass-ceramic article according to any one of aspects 16 to 19, wherein the Na2O concentration at the outer surface of the ion exchange glass-ceramic article is less than 10 mol%.
[0028] According to the 21st aspect disclosed herein, a method for strengthening a glass-ceramic product having a crystalline phase selected from petalite, lithium disilicate and a combination thereof, the method comprising: applying an ion exchange medium to the glass-ceramic product, wherein the ion exchange medium comprises greater than 0 wt % and less than or equal to 20 wt % NaNO3, 80 wt % to less than 100 wt % KNO3, and 0.01 wt % to 0.5 wt % LiNO3.
[0029] According to a 22nd aspect disclosed herein, the method includes the method according to the 21st aspect, wherein the temperature of the ion exchange medium is 380°C to 550°C.
[0030] According to a 23rd aspect disclosed herein, the method includes the method according to aspect 21 or 22, wherein the ion exchange medium is applied to the glass ceramic article for a period of 2 hours to 16 hours.
[0031] According to the 24th aspect disclosed herein, the method includes the method according to any one of aspects 21 to 23, wherein the ion exchange medium is a second ion exchange medium, and the method further includes: applying a first ion exchange medium to the glass ceramic article, wherein the first ion exchange medium contains NaNO3, KNO3 and 0.01 wt% to 0.5 wt% LiNO3, and applying the second ion exchange medium after applying the first ion exchange medium.
[0032] According to a 25th aspect disclosed herein, the method includes the method according to aspect 24, wherein the first ion exchange medium comprises greater than 20 wt % NaNO 3 .
[0033] According to a 26th aspect disclosed herein, the method includes the method according to aspect 24 or 25, wherein the second ion exchange medium comprises greater than 95 wt % and less than 100 wt % KNO 3 and greater than 0 wt % and less than 5 wt % NaNO 3.
[0034] According to the 27th aspect disclosed herein, a method for strengthening a glass-ceramic product having a crystalline phase selected from petalite, lithium disilicate and a combination thereof, the method comprising: applying an ion exchange medium to the glass-ceramic product, wherein the ion exchange medium comprises greater than 20 wt % and less than or equal to 50 wt % NaNO3, 50 wt % to less than 80 wt % KNO3, and 0.01 wt % to 0.5 wt % LiNO3.
[0035] According to a 28th aspect disclosed herein, the method includes the method according to the 27th aspect, wherein the temperature of the ion exchange medium is 380°C to 550°C.
[0036] According to a 29th aspect disclosed herein, the method includes the method according to aspect 27 or 28, wherein the ion exchange medium is applied to the glass ceramic article for a period of 2 hours to 16 hours.
[0037] According to a 30th aspect disclosed herein, the method includes the method according to any one of aspects 27 to 29, wherein the ion exchange medium includes 30 wt % to 50 wt % NaNO 3 and 50 wt % to 70 wt % KNO 3 .
[0038] According to the 31st aspect disclosed herein, a consumer electronic product comprises a shell including a front surface, a rear surface and a side surface; electrical components at least partially located within the shell, the electrical components comprising a controller, a memory and a display, the display being located at the front surface of the shell or adjacent to the front surface of the shell; and a cover substrate disposed above the display, wherein at least one of a portion of the shell or the cover substrate comprises the ion exchange glass ceramic product as described in any one of aspects 1 to 20.
[0039] Additional features and advantages are set forth in the following detailed description, some of which will be apparent to those skilled in the art from the description or may be learned by practicing the embodiments described herein, including the following detailed description, claims, and accompanying drawings.
[0040] It should be understood that both the foregoing general description and the following detailed description describe various embodiments and are intended to provide an overall review or framework for understanding the nature and characteristics of the claimed subject matter. The included drawings provide a further understanding of the various embodiments, and the drawings are incorporated into and constitute a part of this specification. The drawings illustrate the various embodiments described herein and, together with the description, are used to explain the principles and operations of the claimed subject matter.
[0041] This application also includes the following implementation schemes.
[0042] 1. An ion exchange glass ceramic product having a thickness t, wherein:
[0043] The glass article includes a stress that decreases with increasing distance according to a substantially linear function from a depth of about 0.07t to a depth of about 0.26t from an outer surface toward a centerline of the ion-exchanged glass-ceramic article;
[0044] The stress changes from a compressive stress to a tensile stress at a depth of about 0.18t to about 0.25t from the outer surface of the ion-exchanged glass-ceramic article; and
[0045] The absolute value of the maximum compressive stress at the outer surface of the ion-exchanged glass-ceramic article is 1.8 to 2.2 times the absolute value of the maximum central tension (CT) of the ion-exchanged glass-ceramic article; and
[0046] The fracture toughness of the ion-exchanged glass-ceramic article is greater than or equal to 1 MPa√m, as measured by a double cantilever beam method.
[0047] 2. The ion exchange glass-ceramic product according to embodiment 1, wherein the maximum central tension is greater than or equal to 70 MPa.
[0048] 3. The ion-exchanged glass-ceramic article of embodiment 1, wherein the maximum central tension is 80 MPa to 140 MPa.
[0049] 4. The ion exchange glass-ceramic article of any one of embodiments 1-3, wherein the maximum compressive stress is 180 MPa to 350 MPa.
[0050] 5. The ion-exchanged glass-ceramic article of any one of embodiments 1-4, wherein the fracture toughness is 1 MPa√m to 1.5 MPa√m, as measured by a double cantilever beam method.
[0051] 6. The ion exchange glass-ceramic article of any one of embodiments 1-5, wherein the ion exchange glass-ceramic article has a Na2O concentration at an outer surface of less than 10 mol%.
[0052] 7. An ion exchange glass-ceramic article having a thickness t, wherein:
[0053] The Li ion concentration increases from a surface Li ion concentration to a maximum Li ion concentration as the distance from the outer surface of the ion exchange glass-ceramic article increases, wherein the difference between the surface Li ion concentration and the maximum Li ion concentration is less than 5 mol %;
[0054] The Na ion concentration increases from a surface Na ion concentration and then decreases to a minimum Na ion concentration as the distance from the outer surface of the ion-exchanged glass-ceramic article increases, wherein the difference between the surface Na ion concentration and the minimum Na ion concentration is less than 5 mol % and the surface Na ion concentration is less than 10 mol %; and
[0055] The fracture toughness of the ion-exchanged glass-ceramic article is greater than 1 MPa√m, as measured by the double cantilever beam method.
[0056] 8. The ion-exchanged glass-ceramic article of embodiment 7, wherein the concentration of Na ions is greater than 0 mol % throughout the thickness t of the ion-exchanged glass-ceramic article.
[0057] 9. The ion-exchanged glass-ceramic article of Embodiment 8, wherein the concentration of Na ions is greater than 0 mol % and less than 2.5 mol %.
[0058] 10. The ion-exchanged glass-ceramic article of any one of embodiments 7-9, wherein the maximum concentration of Li ions is 19 mol % to 32 mol %.
[0059] 11. The ion-exchanged glass-ceramic article of any one of embodiments 7-10, wherein the fracture toughness is 1 MPa√m to 1.5 MPa√m as measured by the double cantilever beam method.
[0060] 12. The ion exchange glass-ceramic article of any one of embodiments 7-11, further comprising greater than 0 mol% to 6 mol% Al2O3.
[0061] 13. The ion exchange glass-ceramic article of any one of embodiments 7-12, further comprising 0.7 mol % to 2.2 mol % P2O5.
[0062] 14. The ion exchange glass-ceramic article of any one of embodiments 7-13, further comprising 1.7 mol % to 4.5 mol % ZrO2.
[0063] 15. The ion exchange glass-ceramic article of any one of embodiments 7-14, further comprising 60 mol % to 72 mol % SiO2.
[0064] 16. An ion exchange glass ceramic article comprising 1% to 30% residual glass content and 70% to 99% crystalline phase, wherein the crystalline phase is selected from lithium disilicate, petalite, β-quartz, β-spodumene solid solution and combinations thereof; the ion exchange glass ceramic article having a thickness t and comprising stress, wherein the stress decreases with increasing distance from the outer surface toward the center line of the ion exchange glass ceramic article, wherein:
[0065] The stress decreases according to a substantially linear function from a depth of about 0.07t to a depth of about 0.26t from an outer surface of the ion-exchanged glass-ceramic article;
[0066] The stress changes from a compressive stress to a tensile stress at a depth of about 0.18t to about 0.25t from the outer surface of the ion-exchanged glass-ceramic article; and
[0067] The maximum compressive stress at the outer surface of the ion-exchanged glass article is 1.8 to 2.2 times the value of the maximum central tension (CT) of the ion-exchanged glass article.
[0068] 17. The ion-exchanged glass-ceramic article of embodiment 16, wherein the fracture toughness of the ion-exchanged glass-ceramic article is 1 MPa√m to 1.5 MPa√m, as measured by a double cantilever beam method.
[0069] 18. The ion-exchanged glass-ceramic article of embodiment 16 or embodiment 17, wherein the ion-exchanged glass-ceramic is opaque.
[0070] 19. The ion exchange glass-ceramic article of any one of embodiments 16-18, wherein the maximum compressive stress is from 180 MPa to 350 MPa.
[0071] 20. The ion exchange glass-ceramic article of any one of embodiments 16-19, wherein the ion exchange glass-ceramic article has a Na2O concentration at the outer surface of less than 10 mol%.
[0072] 21. A method for strengthening a glass-ceramic product having a crystalline phase selected from petalite, lithium disilicate and combinations thereof, the method comprising:
[0073] An ion exchange medium is applied to the glass ceramic article, wherein the ion exchange medium comprises greater than 0 wt % and less than or equal to 20 wt % NaNO 3 , 80 wt % to less than 100 wt % KNO 3 , and 0.01 wt % to 0.5 wt % LiNO 3 .
[0074] 22. The method of embodiment 21, wherein the temperature of the ion exchange medium is 380°C to 550°C.
[0075] 23. The method of embodiment 22, wherein the ion exchange medium is applied to the glass-ceramic article for a period of time ranging from 2 hours to 16 hours.
[0076] 24. The method of any one of embodiments 21-23, wherein the ion exchange medium is a second ion exchange medium, and the method further comprises:
[0077] A first ion exchange medium is applied to the glass ceramic article, wherein the first ion exchange medium comprises NaNO3, KNO3, and 0.01 wt% to 0.5 wt% LiNO3, and a second ion exchange medium is applied after applying the first ion exchange medium.
[0078] 25. The method of embodiment 24, wherein the first ion exchange medium comprises greater than 20 wt % NaNO3.
[0079] 26. The method of embodiment 24 or embodiment 25, wherein the second ion exchange medium comprises greater than 95 wt % and less than 100 wt % KNO 3 and greater than 0 wt % and less than 5 wt % NaNO 3 .
[0080] 27. A method for strengthening a glass-ceramic product having a crystalline phase selected from petalite, lithium disilicate and combinations thereof, the method comprising:
[0081] An ion exchange medium is applied to the glass ceramic article, wherein the ion exchange medium comprises greater than 20 wt % and less than or equal to 50 wt % NaNO 3 , 50 wt % to less than 80 wt % KNO 3 , and 0.01 wt % to 0.5 wt % LiNO 3 .
[0082] 28. The method of embodiment 27, wherein the temperature of the ion exchange medium is 380°C to 550°C.
[0083] 29. The method of embodiment 28, wherein the ion exchange medium is applied to the glass-ceramic article for a period of time ranging from 2 hours to 16 hours.
[0084] 30. The method of any one of embodiments 27-29, wherein the ion exchange medium comprises 30 wt % to 50 wt % NaNO 3 and 50 wt % to 70 wt % KNO 3 .
[0085] 31. A consumer electronic product comprising:
[0086] a housing, the housing comprising a front surface, a rear surface and side surfaces;
[0087] electrical components at least partially located within the housing, the electrical components including a controller, a memory, and a display, the display being located at or near a front surface of the housing; and
[0088] A cover substrate is disposed above the display.
[0089] Wherein, at least one of a portion of the shell or the cover plate substrate comprises an ion exchange glass ceramic product as described in any one of Embodiments 1-6. BRIEF DESCRIPTION OF THE DRAWINGS
[0091] FIG. 1 is a graph of the concentration of sodium, lithium and potassium elements distributed in a glass-ceramic substrate (Y-axis, in mole % of oxide) as a function of depth from the surface into the thickness of the sample (X-axis, in micrometers or μm) when the glass-ceramic substrate formed of composition A is subjected to a conventional ion exchange treatment;
[0092] 2A and 2B are FSM spectra at 365 mm of a glass-ceramic article subjected to conventional ion exchange treatment;
[0093] FIG3 is an optical micrograph of a glass-ceramic article having the element distribution of FIG1 after exposure to 85° C. / 85% relative humidity for 48 hours;
[0094] FIG4A is an atomic force microscope (AFM) image of the surface roughness of a glass sample consistent with Example A;
[0095] FIG4B is an AFM image of the surface roughness of a glass-ceramic article formed from Composition A subjected to conventional ion exchange treatment;
[0096] Figure 5 is a FSM spectrum at 365 nm of a glass-ceramic article subjected to streak-free ion exchange treatment according to one or more embodiments shown and described herein;
[0097] Figure 6 is a graph of retardation (left Y-axis, in degrees) and stress (right Y-axis, in megapascals (MPa), where compressive stress is positive and tensile stress is negative) as a function of thickness (X-axis, in micrometers or μm) from the surface through the thickness of the sample for a glass-ceramic article subjected to a streak-free ion exchange treatment according to one or more embodiments shown and described herein;
[0098] Figure 7 is a graph of dimensional growth due to ion exchange (Y-axis, in % of length) as related to central tension (X-axis; in MPa) for a glass-ceramic article subjected to streak-free ion exchange treatment according to one or more embodiments shown and described herein;
[0099] Figures 8A-8E is a FSM spectrum at 365 nm of a glass-ceramic article subjected to a single-stripe ion exchange treatment according to one or more embodiments shown and described herein;
[0100] Fig. 9 is a graph of the concentration of sodium, lithium, and potassium elements distributed in a glass-ceramic substrate (Y-axis, in mole % of oxide) as a function of depth from the surface into the thickness of the sample (X-axis, in micrometers or μm) when the glass-ceramic substrate formed of composition A is subjected to a single stripe ion exchange treatment according to one or more embodiments shown and described herein;
[0101] Figures 10A-10H is a FSM spectrum at 365 nm of a glass-ceramic article subjected to a single-stripe ion exchange treatment according to one or more embodiments shown and described herein;
[0102] Fig.11 is a graph of stress (Y-axis, in MPa; compressive stress is positive and tensile stress is negative) of a glass-ceramic article subjected to a single-stripe ion exchange treatment as a function of depth from the surface into the thickness of the sample (X-axis, in micrometers or μm) measured using RNF according to one or more embodiments shown and described herein;
[0103] Fig.12 is a graph of stress (Y-axis, in MPa; compressive stress is positive and tensile stress is negative) of a glass-ceramic article subjected to streak-free ion exchange treatment as a function of depth from the surface into the thickness of the sample (X-axis, in micrometers or μm) as measured using RNF according to one or more embodiments shown and described herein;
[0104] Fig.13 is a graph of applied fracture stress (Y-axis; in MPa) for samples (X-axis) subjected to various ion exchange treatments according to one or more embodiments shown and described herein and tested using a four-point bend test after damage was introduced with 80 grit sandpaper;
[0105] Figures 14A-14C is a graph of asymptotic surface drop test results for samples subjected to various ion exchange treatments (X-axis), wherein failure height is shown on the Y-axis (in cm) according to one or more embodiments shown and described herein;
[0106] Fig.15A is an optical micrograph of a glass-ceramic article subjected to conventional ion exchange treatment before exposure to 85°C / 85% relative humidity aging conditions;
[0107] Fig. 15B yes Fig.15A Optical micrograph of a glass-ceramic product after exposure to aging conditions of 85°C / 85% relative humidity for 144 hours;
[0108] Fig. 15C is an optical micrograph of a glass-ceramic article subjected to streak-free ion exchange treatment according to one or more embodiments shown and described herein after exposure to aging conditions of 85° C. / 85% relative humidity for 48 hours;
[0109] Fig.15D yes Fig. 15COptical micrograph of a glass-ceramic product after exposure to aging conditions of 85°C / 85% relative humidity for 144 hours;
[0110] Fig.16A yes Fig. 15B Graph of the distribution of carbon, hydrogen, Li2O, Na2O, Al2O3 and P2O5 elements in a glass-ceramic substrate (Y-axis, in mole % of oxides) as a function of depth from the surface into the thickness of the sample (X-axis, in micrometers or μm);
[0111] Fig. 16B yes Fig.15D Graph of the distribution of carbon, hydrogen, Li2O, Na2O, Al2O3 and P2O5 elements in a glass-ceramic substrate (Y-axis, in mole % of oxides) as a function of depth from the surface into the thickness of the sample (X-axis, in micrometers or μm);
[0112] Fig.17 is a schematic diagram of the setup used in the dual cantilever beam method for measuring fracture toughness;
[0113] Fig.18A is a plan view of an exemplary electronic device including any of the enhanced articles disclosed herein; and
[0114] Fig.18B yes Fig.18A A perspective view of an exemplary electronic device. DETAILED DESCRIPTION
[0115] Various embodiments will be described in detail below, examples of which are shown in the accompanying drawings. Whenever possible, the same reference numerals are used throughout the drawings to refer to the same or like parts.
[0116] Definition and measurement techniques
[0117] Herein, ranges may be expressed as starting from "about" one specific value and / or ending at "about" another specific value. When such a range is expressed, another embodiment includes starting from the one specific value and / or ending at the other specific value. Similarly, when the antecedent "about" is used to express a numerical value as an approximate value, it should be understood that the specific numerical value constitutes another embodiment. It should also be understood that the endpoints of each range are important both in relation to and independently of the other endpoint. When such a range is expressed, the embodiment includes starting from a specific value and / or ending at another specific value. Similarly, when the antecedent "about" is used to express a numerical value as an approximate value, it should be understood that the specific numerical value constitutes another embodiment. Regardless of whether the numerical value or endpoint of the range in the specification is stated using "about", the numerical value or endpoint of the range is intended to include two embodiments: one modified with "about" and the other not modified with "about". It should also be understood that the endpoints of each range are important both in relation to and independently of the other endpoint.
[0118] As used herein, the terms "substantially," "substantially," and variations thereof are intended to mean that the feature being described is equal to or approximately equal to a value or description. For example, a "substantially flat" surface is intended to mean a flat or approximately flat surface. Additionally, as defined above, "substantially similar" is intended to mean that two values are equal or approximately equal. In some embodiments, "substantially similar" can mean values that are within about 10% of each other, such as within about 5% of each other, or within about 2% of each other.
[0119] Directional terms used herein—eg, up, down, right, left, front, back, top, bottom—are used only with reference to the drawings in which they are drawn and are not intended to imply an absolute orientation.
[0120] The disclosed ranges should be understood to include any and all subranges or any and all individual values included in each range, and to provide support for claims describing these subranges or individual values. For example, a stated range of 1 to 10 should be understood to include any and all subranges between a minimum value of 1 and a maximum value of 10 or individual values therebetween (including and / or excluding endpoints), and to provide support for claims describing these subranges or individual values; that is, all subranges starting with a minimum value of 1 or greater and ending with a maximum value of 10 or less (e.g., 5.5 to 10, 2.34 to 3.56, etc.) or any value from 1 to 10 (e.g., 3, 5.8, 9.9994, etc.).
[0121] As used herein, "depth of compression" or "DOC" refers to the depth of the compressive stress (CS) layer, and it is the depth at which the stress within the glass-ceramic article changes from compressive stress to tensile stress, and its stress value is zero. Compressive stress is expressed here as positive (>0) stress, and tensile stress is expressed as negative (<0) stress. However, unless otherwise stated, in this specification, the numerical values of tensile stress and compressive stress are expressed as positive or absolute values. Depending on the ion exchange treatment method, DOC can be measured by FSM or scattered light polarizer (SCALP). If the stress in the glass article is generated by exchanging potassium ions into the glass article, FSM is used to measure DOC. If the stress is generated by exchanging sodium ions into the glass article, SCALP is used to measure DOC. If the stress in the glass article is produced by exchanging both potassium and sodium ions into the glass, the DOC is measured by SCALP because the depth of exchange of sodium is considered to be indicative of the DOC, while the depth of exchange of potassium ions is indicative of the magnitude of the change in compressive stress (but not a change in stress from compressive to tensile); the depth of exchange of potassium ions in such a glass article is measured by FSM.
[0122] The various embodiments described herein, in particular, compressive stress is measured by a surface stress meter (FSM), using a commercial instrument such as FSM-6000 manufactured by Orihara Industrial Co., Ltd., Japan. As will be discussed in more detail herein, surface stress measurement relies on the accurate measurement of the stress optical coefficient (SOC), which is related to the birefringence of the glass ceramic. SOC is then measured according to Scheme C (glass disk method) entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient" described in ASTM Standard C770-16, the contents of which are incorporated herein by reference in their entirety. If a low refractive index layer is formed, the surface compressive stress (and the compressive stress of the low refractive index layer) is measured by the birefringence of the first transmission (coupling) resonance of the low refractive index layer in the prism coupling measurement, and the layer depth of the low refractive index layer is measured by the spacing between the first and second transmission resonances or the width of the first transmission resonance.
[0123] A stress profile plot from approximately the knee to the maximum CT can be obtained by a refracted near field (RNF) method as described in U.S. Pat. No. 8,854,623, entitled “Systems and methods for measuring a profile characteristic of a glass sample,” which is incorporated herein by reference in its entirety. The RNF plot is force balanced and calibrated to a maximum center tension (also referred to as peak center tension) value provided by a SCALP measurement. Specifically, the RNF method includes placing a glass article near a reference block, generating a polarization-switched beam that switches between orthogonal polarizations at a frequency of 1 Hz to 50 Hz, measuring the amount of power in the polarization-switched beam, and generating a polarization-switched reference signal, wherein the amount of power measured in each orthogonal polarization is within 50% of each other. The method also includes transmitting the polarization-switched beam through the glass sample and the reference block to penetrate to different depths in the glass sample, and then transmitting the transmitted polarization-switched beam to a signal light detector using a relay optical system, and the signal light detector generates a polarization-switched detector signal. The method also includes dividing the detector signal by the reference signal to form a normalized detector signal, and determining a profile characteristic of the glass sample from the normalized detector signal.
[0124] The diagram of the stress distribution curve can be obtained using a combination of RNF, SCALP and FSM. FSM is used to obtain a diagram of the stress distribution curve portion near the surface, while RNF is used together with SCALP to obtain a shape diagram of the stress distribution curve portion that exceeds the knee depth and passes through the tensile stress portion of the stress distribution curve. The parts obtained by FSM, RNF and SCALP are spliced together to provide the following complete diagram of the stress distribution curve. RNF is force balanced and calibrated to match the SCALP center tension. Force balance is performed by moving the neutral axis so that the tensile stress area below the illustrated neutral axis matches the compressive stress area above the illustrated neutral axis. After force balancing and calibrating the RNF, the surface peak diagram obtained by the FSM is spliced into the RNF diagram of the distribution curve, thereby replacing the corresponding RNF diagram portion. Repeat the process of force balance, calibration to the SCALP center tension and splicing until convergence is reached, that is, the diagram of the distribution curve does not change substantially with further repetition of the process. When appropriate and necessary, standard smoothing techniques can be used to remove measurement noise.
[0125] The concentration profile of various constituent components in the glass, such as alkali metal constituent components, is measured by electron probe microanalysis (EPMA). For example, EPMA can be used to identify compressive stresses in the glass due to ion exchange of alkali metal ions into the glass. In some embodiments, glow discharge optical emission spectroscopy (GdOES) is used to measure the average surface concentration level (e.g., the average surface concentration level within 100 nm from the glass surface).
[0126] The fracture toughness measurements were performed using the dual cantilever beam (DCB) method. The DCB specimen geometry is shown in Fig.17 , where the key parameters are the crack length a, the applied load P, the cross-sectional dimensions w and 2h, and the thickness b of the crack guiding groove. The samples are formed from the same composition as the sample to be tested but have not undergone ion exchange, and are prepared by cutting the glass into rectangles with a width 2h = 1.25 centimeters (cm) and a thickness ranging from w = 0.3 millimeters (mm) to 1 mm, and the total length of the sample varies from 5 cm to 10 cm. Each glass sample has holes drilled with a diamond drill bit on both ends to provide a way to attach the sample to a sample holder and a load. A wafer saw with a diamond blade is used to cut the crack "guiding groove" b along the length of the sample on two flat faces, leaving a "web" of material that is approximately half the total plate thickness ( Fig.17 b) in the figure, and the height of 180 μm is the blade thickness or kerf. The high-precision dimensional tolerance of the saw minimizes the differences between samples. The saw was also used to cut an initial crack with a=15 mm, which produced a very thin wedge of material near the crack tip (due to the blade curvature), making it easier to initiate cracks in the sample.
[0127] The crack guiding groove b maintains the crack in the plane and prevents it from growing out of the crack plane. The sample is mounted in a metal sample holder by hooking a wire into the bottom hole of the sample. The sample is also supported on the opposite end to keep the sample level under low load conditions. A spring connected in series with a force sensor (FUTEK, LSB200) is hooked to the upper hole and then stretched using a rope and a high-precision slide to gradually apply the load. The crack is monitored using a microscope (5–10 μm resolution) connected to a digital camera and a computer.
[0128] By maintaining tight tolerances on dimensional parameters, the applied stress intensity K is calculated using equation (1) P , where the input parameters are shown in Fig.17 :
[0129]
[0130] For each sample, a crack is initiated at the tip of the web, and then the initial crack is carefully grown under subcriticality until the ratio of size a / h is greater than 1.5, which is used in equation (1) to accurately calculate stress intensity. At this time, a mobile display mirror with a resolution of 5 μm is used to measure and record the crack length a. Then a drop of toluene is dripped into the crack groove, and wicks along the entire length of the groove under the action of capillary force, which prevents the crack from moving unless loaded to the fracture toughness. Toluene, heavy mineral oil, silicone oil and other organic substances act as a barrier between atmospheric moisture and the glass surface and prevent subcritical crack growth. Subsequently, the load is increased until the sample breaks, and the critical stress intensity is calculated based on the failure load and sample size. All samples are measured using optical microscopy after the test to ensure that the correct sample size is used in the K calculation. When the fracture toughness of the ion exchange sample is to be tested, the sample with the same composition as the sample to be tested is measured as described above, but the sample to be tested has been subjected to ion exchange before this measurement.
[0131] The term "formed from" may mean one or more of comprising, consisting essentially of, or consisting of. For example, a component formed from a particular material may comprise the particular material, consist essentially of the particular material, or consist of the particular material.
[0132] Overview of glass ceramic products
[0133] The glass ceramic products of various embodiments include petalite and lithium pyrosilicate as the main crystalline phases, and may optionally further include a lithium aluminum silicate (LAS) crystalline phase. The glass ceramic products include a surface layer having a sodium content of less than or equal to 10 mol%. After ion exchange treatment, the glass ceramic products described herein exhibit increased stored energy (central tension), increased fracture toughness, and are not brittle.
[0134] LiAlSi4O 10 ) is a monoclinic crystal with a three-dimensional framework structure and a layered structure with folded Si2O5 layers connected by Li and Al tetrahedra. Li is tetrahedral coordinated with oxygen. Petalite is a lithium source and is used as a low thermal expansion phase to improve the thermal shock resistance of glass ceramics or ceramic parts. Lithium disilicate (Li2Si2O5) is an orthorhombic crystal based on a wavy sheet of {Si2O5} tetrahedral array. The shape of the crystal is usually plate-like or lath-like with a distinct cleavage plane. Due to its randomly oriented interlocking crystal microstructure, glass ceramics based on lithium disilicate have highly desirable mechanical properties, including high bulk strength and fracture toughness. The crystal structure forces cracks to propagate through the material through a tortuous path around the interlocking crystals, thereby improving strength and fracture toughness.
[0135] There are two large families of lithium disilicate glass-ceramics. The first group includes lithium disilicate glass-ceramics doped with cerium dioxide and precious metals such as silver. They can be photo-nucleated by ultraviolet light and subsequently heat-treated to produce strong glass-ceramics, such as The second family of lithium disilicate glass-ceramics is nucleated by the addition of P2O5, where the nucleating phase is Li3PO4. P2O5 nucleated lithium disilicate glass-ceramics have been developed for a variety of applications such as high temperature sealing materials, magnetic disks for computer hard drives, transparent armor, and dental applications.
[0136] The glasses and glass ceramics described herein can be generally described as lithium-containing aluminosilicate glasses or glass ceramics, and include SiO2, Al2O3 and Li2O. In addition to SiO2, Al2O3 and Li2O, the glasses and glass ceramics specifically implemented herein can further contain alkali metal oxides, such as Na2O, K2O, Rb2O or Cs2O, as well as P2O5 and ZrO2 and various other components as described below. In one or more embodiments, the crystalline phase includes petalite and lithium disilicate, but depending on the composition of the precursor glass, β-spodumene solid solution, β-quartz, metasilicate, lithium phosphate and zirconium may also be present. In some embodiments, the glass-ceramic composition has a residual glass content of 1 to 30 wt%, 1 to 25 wt%, 1 to 20 wt%, 1 to 15 wt%, 1 to 10 wt%, 1 to 5 wt%, 5 to 30 wt%, 5 to 25 wt%, 5 to 20 wt%, 5 to 15 wt%, 5 to 10 wt%, 10 to 30 wt%, 10 to 25 wt%, 10 to 20 wt%, 10 to 15 wt%, 15 to 30 wt%, 15 to 25 wt%, 15 to 20 wt%, 20 to 30 wt%, 20 to 25 wt%, or 25 to 30 wt%, as determined by Rietveld analysis of the XRD pattern. It will be appreciated that the residual glass content can be within the subranges formed by any and all of the aforementioned endpoints. Thus, in some embodiments, the glass-ceramic article has 70 to 99 weight %, 70 to 95 weight %, 70 to 90 weight %, 70 to 85 weight %, 70 to 80 weight %, 70 to 75 weight %, 75 to 99 weight %, 75 to 95 weight %, 75 to 90 weight %, 75 to 85 weight %, 75 to 80 weight %, 80 to 99 weight %, 80 to 95 weight %, 80 to 90 weight %, 80 to 85 weight %, 85 to 99 weight %, 85 to 95 weight %, 85 to 90 weight %, 90 to 99 weight %, 90 to 95 weight %, or 95 to 99 weight % crystalline phase.
[0137] SiO2 is the main glass former, which can play a role in stabilizing the network structure of glasses and glass ceramics. In some embodiments, the glass or glass ceramic composition comprises 55 to 80 mol % SiO2. In some embodiments, the glass or glass ceramic composition comprises 60 to 72 mol % SiO2. In some embodiments, the glass or glass ceramic composition may comprise 55 to 80 mol %, 55 to 77 mol %, 55 to 75 mol %, 55 to 73 mol %, 60 to 80 mol %, 60 to 77 mol %, 60 to 75 mol %, 60 to 73 mol %, 60 to 72 mol % SiO2, or any and all subranges formed by any of these endpoints.
[0138] The concentration of SiO2 should be high enough (greater than 55 mol%) to form a petalite crystalline phase when the precursor glass is heat treated and converted into a glass-ceramic. In other words, the concentration of SiO2 should be high enough to obtain both lithium silicate and petalite phases. The amount of SiO2 can be limited to control the melting temperature (200 poise temperature) because the melting temperature of pure SiO2 or high SiO2 glass is undesirably high.
[0139] Similar to SiO2, Al2O3 can also provide stability to the network and also provide improved mechanical properties and chemical durability. However, if the amount of Al2O3 is too high, the fraction of lithium silicate crystals may be reduced, which may reach a point where an interlocking structure cannot be formed. The amount of Al2O3 can be tailored to control the viscosity. Further, if the amount of Al2O3 is too high, the viscosity of the melt generally also increases. In some embodiments, the glass or glass ceramic composition may include 0 to 6 mol% Al2O3. In some embodiments, the glass or glass ceramic composition can include 0 to 6 mol%, 0 to 5 mol%, 0 to 4 mol%, 0 to 3 mol%, 0 to 2 mol%, 0 to 1 mol%, greater than 0 to 6 mol%, greater than 0 to 5 mol%, greater than 0 to 4 mol%, greater than 0 to 3 mol%, greater than 0 to 2 mol%, greater than 0 to 1 mol%, 0.5 to 6 mol%, 0.5 to 5 mol%, 0.5 to 4 mol%, 0.5 to 3 mol%, 0.5 to 2 mol%, 0.5 to 1 mol%, 1 to 6 mol%, 1 to 5 mol%, 1 to 4 mol%, 1 to 3 mol%, 1 to 2 mol%, 2 to 6 mol%, 2 to 5 mol%, 2 to 4 mol%, 2 to 3 mol%, 3 to 6 mol%, 3 to 5 mol%, 3 to 4 mol%, 4 to 6 mol%, 4 to 5 mol%, or 5 to 6 mol% Al2O3, or any and all subranges formed by any of these endpoints.
[0140] In the glasses and glass ceramics described herein, Li2O contributes to the formation of both petalite and lithium silicate crystalline phases. In order to obtain petalite and lithium silicate as the main crystalline phases, it is desirable to have 14 mol% or more of Li2O in the composition. However, if the concentration of Li2O is too high - greater than 36 mol% - the composition becomes very fluid and the feed viscosity is too low to form a sheet. In some specific embodiments, the glass or glass ceramic may contain 20 mol% to 32 mol% of Li2O. In some embodiments, the glass or glass ceramic composition can include 20 to 32 mol%, 20 to 30 mol%, 20 to 28 mol%, 20 to 26 mol%, 20 to 24 mol%, 22 to 32 mol%, 22 to 30 mol%, 22 to 28 mol%, 22 to 26 mol%, 22 to 24 mol%, 24 to 32 mol%, 24 to 30 mol%, 24 to 28 mol%, 24 to 26 mol%, 26 to 32 mol%, 26 to 30 mol%, 26 to 28 mol%, 28 to 32 mol%, 28 to 30 mol%, or 30 to 32 mol% LiO, or any and all subranges formed by any of these endpoints.
[0141] As described above, Li2O is generally used to form a glass-ceramic of a specific embodiment, but other alkali metal oxides (such as K2O and Na2O) tend to reduce the formation of glass-ceramics and form aluminosilicate residual glass instead of a ceramic phase in the glass-ceramic. It has been found that more than 10 mol% of Na2O or K2O or a combination thereof results in an undesirable amount of residual glass, which can cause deformation and undesirable microstructure during crystallization from the perspective of mechanical properties. In addition, Na2O levels greater than 10 mol% can make the surface susceptible to subsurface hydration, which can lead to the growth of sodium carbonate crystals on the surface. These sodium carbonate crystals can then produce surface haziness on the glass-ceramic. However, levels below 5 mol% may be beneficial for ion exchange, which allows for higher surface compression and / or metering. Generally, the compositions described herein have a low amount of non-lithium alkali metal oxides. In some embodiments, the glass or glass-ceramic composition may contain 0 to 5 mol% of R2O, wherein R is one or more of the alkali metal cations Na and K. In some embodiments, the glass or glass ceramic composition may include 1 to 4 mol% of RO, wherein R is one or more of the alkali metal cations Na and K. In some embodiments, the glass or glass ceramic composition may include 0 to 5 mol%, 0 to 4 mol%, 0 to 3 mol%, 0 to 2 mol%, 0 to 1 mol%, >0 to 5 mol%, >0 to 4 mol%, >0 to 3 mol%, >0 to 2 mol%, >0 to 1 mol%, 1 to 5 mol%, 1 to 4 mol%, 1 to 3 mol%, 1 to 2 mol%, 2 to 5 mol%, 2 to 4 mol%, 2 to 3 mol%, 3 to 5 mol%, 3 to 4 mol%, or 4 to 5 mol% of NaO or KO, or combinations thereof. It should be understood that the RO concentration can be within a subrange formed by any and all of the aforementioned endpoints.
[0142] Glass and glass ceramic compositions may include P2O5. P2O5 may be used as a nucleating agent to produce bulk nucleation of a crystalline phase from the glass and glass ceramic compositions. If the concentration of P2O5 is too low, the precursor glass crystallizes, but only at higher temperatures (due to lower viscosity); however, if the concentration of P2O5 is too high, crystallization may be difficult to control after cooling during formation of the precursor glass. Embodiments may include >0 to 3 mol % P2O5. Other embodiments may include >0.7 to 2.2 mol % P2O5. Specific embodiments of the composition may include >0 to 3 mol%, >0 to 2.5 mol%, >0 to 2.2 mol%, >0 to 2 mol%, >0 to 1.5 mol%, >0 to 1.2 mol%, >0 to 1 mol%, 0.7 to 3 mol%, 0.7 to 2.5 mol%, 0.7 to 2.2 mol%, 0.7 to 2 mol%, 0.7 to 1.5 mol%, 0.7 to 1.2 mol%, 0.7 to 1 mol%, 1 to 3 mol%, 1 to 2.5 mol%, 1 to % PO5, or any and all subranges formed by any of these endpoints.
[0143] In the glasses and glass ceramics described herein, the addition of ZrO2 can improve the stability of the Li2O-Al2O3-SiO2-P2O5 glass, which works by significantly reducing the glass crystallization during forming and lowering the liquidus temperature. At a concentration greater than 4 mol%, ZrO2 can form a main liquidus phase at high temperatures, which significantly reduces the liquidus viscosity. When the glass contains more than 1 mol% ZrO2, a transparent glass can be formed. The addition of ZrO2 can also reduce the size of the petalite grains, which helps to form transparent glass ceramics. In some embodiments, the glass or glass ceramic composition may include 1.7 to 4.5 mol% ZrO2. In some embodiments, the glass or glass ceramic composition may include 2 to 4 mol% ZrO2. In some embodiments, the glass or glass ceramic composition can include 1.7 to 4.5 mol%, 1.7 to 4 mol%, 1.7 to 3.5 mol%, 1.7 to 3 mol%, 1.7 to 2.5 mol%, 1.7 to 2 mol%, 2 to 4.5 mol%, 2 to 4 mol%, 2 to 3.5 mol%, 2 to 3 mol%, 2 to 2.5 mol%, 2.5 to 4.5 mol%, 2.5 to 4 mol%, 2.5 to 3.5 mol%, 2.5 to 3 mol%, 3 to 4.5 mol%, 3 to 4 mol%, 3 to 3.5 mol%, 3.5 to 4.5 mol%, 3.5 to 4 mol%, 4 to 4.5 mol% ZrO2, or any and all subranges formed by any of these endpoints.
[0144] B2O3 reduces the melting temperature of the glass precursor. In addition, adding B2O3 in the precursor glass and therefore adding B2O3 in the glass ceramic helps to achieve an interlocking crystal microstructure and can also improve the damage resistance of the glass ceramic. When the boron in the residual glass is not charge balanced by alkali metal oxides or divalent cation oxides (e.g., MgO, CaO, SrO, BaO and ZnO), it will be in a three-coordinate state (or a three-coordinate boron) and open the glass structure. The network around these three-coordinate boron atoms is not as hard as tetrahedral coordination (or four-coordinate) boron. Without being limited to theory, it is believed that, compared to four-coordinate boron, precursor glasses and glass ceramics including three-coordinate boron can allow a certain degree of deformation before crack formation. Due to the allowance of certain deformation, the Vickers indentation crack initiation threshold is increased. The fracture toughness of precursor glasses and glass ceramics including three-coordinate boron can also be increased. Without being limited by theory, it is believed that the presence of boron in the residual glass (and precursor glass) of glass-ceramic reduces the viscosity of residual glass (or precursor glass), which promotes the growth of lithium silicate crystals, especially promotes the growth of large crystals with high aspect ratio. A larger amount of tricoordinate boron (relative to tetracoordinate boron) is considered to make glass-ceramic show a larger Vickers indentation crack initiation load. In some embodiments, the amount of tricoordinate boron (as total B2O3 percentage) can be 40% or greater, 50% or greater, 75% or greater, 85% or greater or even 95% or greater. Generally, the amount of boron needs to be controlled to maintain the chemical durability and mechanical strength of the ceramicized bulk glass-ceramic. In other words, the amount of boron should be limited to less than 5 mole %, to maintain chemical durability and mechanical strength.
[0145] In one or more embodiments, the glasses and glass ceramics herein may include 0 to 2 mol % B2O3. In some embodiments, the glass or glass ceramic composition may include 0 to 2 mol %, 0 to 1.5 mol %, 0 to 1 mol %, 0 to 0.5 mol %, >0 to 2 mol %, >0 to 1.5 mol %, >0 to 1 mol %, >0 to 0.5 mol %, 0.5 to 2 mol %, 0.5 to 1.5 mol %, 0.5 to 1 mol %, 1 to 2 mol %, 1 to 1.5 mol %, 1.5 to 2 mol % B2O3, or any and all subranges formed by any of these endpoints.
[0146] MgO can enter the petalite crystal in the form of partial solid solution. In one or more embodiments, the glasses and glass ceramics described herein may include 0 to 1 mol%, 0 to 0.75 mol%, 0 to 0.5 mol%, 0 to 0.25 mol%, >0 to 1 mol%, >0 to 0.75 mol%, >0 to 0.5 mol%, >0 to 0.25 mol%, 0.25 to 1 mol%, 0.25 to 0.75 mol%, 0.25 to 0.5 mol%, 0.5 to 1 mol%, 0.5 to 0.75 mol%, 0.75 to 1 mol% MgO, or any and all subranges formed by any of these endpoints.
[0147] ZnO can enter petalite crystals in the form of partial solid solution. In one or more embodiments, the glass and glass ceramics herein may include 0 to 1 mol % of ZnO. In one or more embodiments, the glass and glass ceramics described herein may include 0 to 1 mol %, 0 to 0.75 mol %, 0 to 0.5 mol %, 0 to 0.25 mol %, >0 to 1 mol %, >0 to 0.75 mol %, >0 to 0.5 mol %, >0 to 0.25 mol %, 0.25 to 1 mol %, 0.25 to 0.75 mol %, 0.25 to 0.5 mol %, 0.5 to 1 mol %, 0.5 to 0.75 mol %, 0.75 to 1 mol % of ZnO, or any and all subranges formed by any of these endpoints.
[0148] In one or more embodiments, the glasses and glass-ceramics may contain 0 to 0.5 mol % SnO 2 or another fining agent. In some embodiments, the glass or glass ceramic composition can include 0 to 0.5 mol%, 0 to 0.4 mol%, 0 to 0.3 mol%, 0 to 0.2 mol%, 0 to 0.1 mol%, 0.05 to 0.5 mol%, 0.05 to 0.4 mol%, 0.05 to 0.3 mol%, 0.05 to 0.2 mol%, 0.05 to 0.1 mol%, 0.1 to 0.5 mol%, 0.1 to 0.4 mol%, 0.1 to 0.3 mol%, 0.1 to 0.2 mol%, 0.2 to 0.5 mol%, 0.2 to 0.4 mol%, 0.2 to 0.3 mol%, 0.3 to 0.5 mol%, 0.3 to 0.4 mol%, or 0.4 to 0.5 mol% SnO2, or any and all subranges formed by any of these endpoints.
[0149] Due to the raw materials and / or equipment used to produce the glass or glass-ceramic compositions of various embodiments, some impurities or components that are unintentionally added may be present in the final glass or glass-ceramic compositions. These materials can be present in a small amount in the glass or glass-ceramic compositions, and are referred to herein as "inclusion materials". "Inclusion materials" as used herein can be present in an amount less than 1000ppm. In some embodiments, the glass or glass-ceramic compositions may further include inclusion materials, for example, TiO2, MnO, ZnO, Nb2O5, MoO3, Ta2O5, WO3, Y2O3, La2O3, HfO2, CdO, As2O3, Sb2O3, sulfur-based compounds (e.g., sulfates), halogens, or combinations thereof. In some embodiments, antimicrobial components, chemical clarifiers, or other additional components may be included in the glass or glass-ceramic compositions.
[0150] In some embodiments, the glasses and / or glass-ceramics described herein can be fabricated into sheets by processes including, but not limited to, fusion forming, slot drawing, float forming, rolling, and other sheet forming processes known to those skilled in the art.
[0151] The article formed by the glass ceramics described herein can have any suitable thickness, which can vary according to the specific application using the glass ceramics. Glass sheets and or glass ceramic embodiments can have a thickness of 0.4mm to 10mm. The thickness of some embodiments can be less than or equal to 6mm, less than or equal to 5mm, less than or equal to 3mm, less than or equal to 2mm, less than or equal to 1.0mm, less than or equal to 750μm, less than or equal to 500μm, or less than or equal to 250μm. The thickness of some glass or glass ceramic sheet embodiments can be 200μm to 5mm, 500μm to 5mm, 200μm to 4mm, 200μm to 2mm, 400μm to 5mm or 400μm to 2mm. Some glass or glass ceramic sheet embodiments may have a thickness of 250 μm to 5 mm, 400 μm to 4 mm, 350 μm to 3 mm, 450 μm to 2 mm, 500 μm to 1 mm, or 550 μm to 750 μm. In some embodiments, the thickness may be 3 mm to 6 mm, or 0.8 mm to 3 mm. It should be understood that the article thickness may be within a subrange formed by any and all of the aforementioned endpoints.
[0152] In various embodiments described herein, the glass-ceramic is chemically strengthened, for example, by ion exchange treatment, to increase the chemical durability and damage resistance of the glass-ceramic while enabling metrology measurements and preventing the formation of a fog layer under high humidity conditions.
[0153] When the glass-ceramics described herein are subjected to conventional ion exchange treatments (e.g., ion exchange treatments with molten sodium nitrate, potassium nitrate, or mixed sodium nitrate / potassium nitrate salts), the resulting glass-ceramics can have high stored energy and a maximum central tension of about 70 MPa to about 140 MPa. These glass articles can also exhibit high fracture toughness (K according to a standard V-notch test). 1C is 1.1MPa√m, or K is measured by the double cantilever beam (DCB) method 1C 1.32MPa*m 1 / 2 ), and are non-brittle at a thickness of 0.8 mm, where glass would be brittle. These glass-ceramics may also exhibit desirable mechanical properties.
[0154] However, the crystalline phases of these glass ceramics may also undergo ion exchange during the ion exchange treatment, for example, when the lithium in the lithium disilicate crystalline phase is exchanged with sodium in the ion exchange bath, this can form a highly sodium-rich low refractive index surface layer (i.e., a layer with a lower refractive index than the glass ceramic product), as shown in Figure 1. Specifically, the ion exchange between lithium disilicate and sodium ions can result in low refractive index silicates added to the glass phase of the glass ceramic and the formation of sodium silicate and sodium disilicate in the surface layer. Figure 1 is a graph of the distribution of sodium, lithium and potassium in a glass ceramic product having composition A in Table 1 after ion exchange in a mixed KNO3 / NaNO3 salt containing less than 0.04 wt% LiNO3. In order to produce a glass ceramic product of composition A (such as a sample having composition A for use described below), the product is heated at 570°C for 4 hours, then heated at 740°C for 1 hour, and then subjected to typical cooling of a glass ceramic product. After the aforementioned ceramizing cycle, the article has 9 to 15 weight % of a residual glass phase, 40-48 weight % of a lithium disilicate crystalline phase, 39-45 weight % of a lithium feldspar crystalline phase, and less than about 3 weight % of a lithium metasilicate crystalline phase, wherein each crystalline phase is measured by x-ray diffraction and the standard deviation of the main phase is about 1.2 weight %.
[0155] Table 1:
[0156] Composition A <![CDATA[SiO2]]> 70.65 <![CDATA[Al2O3]]> 4.20 <![CDATA[Li2O]]> 22.10 <![CDATA[Na2O]]> 0 <![CDATA[K2O]]> 0 <![CDATA[P2O5]]> 0.80 <![CDATA[ZrO2]]> 2.00 <![CDATA[SnO2]]> 0.15 <![CDATA[B2O3]]> 0.00 <![CDATA[Li2O / R2O]]> 1.00 <![CDATA[R2O / Al2O3]]> 5.26
[0157] As shown in FIG1 , the surface layer is rich in sodium, wherein sodium is ion-exchanged with lithium ions and both the glass and crystalline phases are ion-exchanged.
[0158] Figures 2A and 2B are FSM images taken at a wavelength of 365 nm. As shown in Figure 2A, since the refractive index of the surface layer is lower than that of the glass-ceramic product, the FSM image of the product is blurred, which makes it unreliable to use FSM as a quality control method to monitor the ion exchange process, especially when the thickness of the ion exchange layer is less than about 3 μm.
[0159] In addition, the extremely low amount of lithium poisoning in the salt bath prevents the formation of a high stress layer generated by the ion exchange of sodium ions with lithium in lithium disilicate. In other words, 0.04 wt% LiNO3 in the ion exchange bath is sufficient to prevent the formation of streaks, as shown in FIG2B. To prevent lithium poisoning, about 0.01 m3 of LiNO3 is exchanged per 1 kg of salt. 2 After cleaning the glass ceramic, the salt in the tank needs to be replaced.
[0160] In addition, this sodium-rich surface layer makes the glass-ceramic surface susceptible to subsurface hydration, which can lead to the growth of sodium carbonate crystals on the surface, which in turn can produce surface haze, as shown in FIG. FIG. 3 is an optical micrograph of a glass article having the element distribution of FIG. 1 after exposure to 85° C., 85% relative humidity for 48 hours. The dendritic growth shown in FIG. 3 is sodium carbonate crystals. More specifically, sodium carbonate crystal growth occurs when hydronium ions from water exchange sodium ions and move into the glass subsurface layer, sodium ions come out of the glass surface, and over time, Na2CO3 is formed on the glass by the reaction of the sodium ions with atmospheric CO2. This growth of sodium carbonate can occur in the presence of atmospheric moisture on the glass for a longer period of time, for example, when the part is packaged in a high humidity environment and the atmospheric moisture is trapped between the glass surface and the packaging film.
[0161] The production of a sodium-rich surface layer also makes the surface susceptible to preferential etching and pitting during polishing and washing, as shown in Figures 4A and 4B. Specifically, Figures 4A and 4B are atomic force microscope (AFM) images of a 500nm x 500nm sample that has been ion exchanged, polished, and washed. Figure 4A depicts the surface roughness of a glass article formed from a glass composition having the following nominal composition and ion exchanged according to a conventional ion exchange process as in Example A, wherein the nominal composition is in mole % 71SiO2; 1.9B2O3; 12.8Al2O3; 2.4Na2O; 8.2Li2O; 2.9MgO; 0.8ZnO; 0.02Fe2O3; 0.01ZrO2; 0.06SnO2. Figure 4B depicts the surface roughness of a glass-ceramic formed from composition A and ion exchanged in a mixed KNO3 / NaNO3 salt containing less than 0.04 wt% LiNO3. Due to the low chemical durability of the sodium-rich surface layer, polishing and washing can result in high surface roughness, which reduces the durability of coatings that can be used for cover glass applications. These coatings can provide scratch resistance, anti-reflection, oleophobic or hydrophobic properties to the cover glass, for example but not limited to.
[0162] In various embodiments described herein, the glass-ceramic is chemically strengthened by an ion exchange process to improve the chemical durability and damage resistance of the glass-ceramic while enabling metrology measurements and preventing the formation of a fog layer under high humidity conditions. Embodiments of the ion exchange process will now be described in more detail.
[0163] Single stripe ion exchange treatment
[0164] In various embodiments, ion exchange treatment of the glass-ceramic article results in a waveguide layer that produces one fringe per polarization state in the FSM measurement, referred to herein as a "single fringe IOX." In these embodiments, the rate of ion exchange of sodium for lithium is such that the refractive index of the surface layer decreases less than the rate of increase in the refractive index due to ion exchange of potassium for sodium in the surface layer, thereby allowing the formation of a waveguide layer.
[0165] In various embodiments, the single stripe IOX treatment includes applying an ion exchange medium to one or more surfaces of the glass-ceramic article. The ion exchange medium can be a molten salt bath, a solution, a paste, a gel, or another suitable medium comprising KNO3, NaNO3, and LiNO3.
[0166] In various embodiments, the ion exchange medium comprises greater than 0 wt % NaNO3 and less than or equal to about 20 wt % NaNO3, based on the total amount of NaNO3 and KNO3 in the ion exchange medium. For example, the ion exchange medium of various embodiments may comprise >0 wt % to 20 wt %, >0 wt % to 15 wt %, >0 wt % to 12 wt %, >0 wt % to 10 wt %, >0 wt % to 7.5 wt %, >0 wt % to 5 wt %, 2.5 wt % to 20 wt %, 2.5 wt % to 15 wt %, 2.5 wt % to 12 wt %, 2.5 wt % to 10 wt %, 2.5 wt % to 7.5 wt %, 2.5 % to 5 wt%, 5 wt% to 20 wt%, 5 wt% to 15 wt%, 5 wt% to 12 wt%, 5 wt% to 10 wt%, 5 wt% to 7.5 wt%, 7.5 wt% to 20 wt%, 7.5 wt% to 15 wt%, 7.5 wt% to 12 wt%, 7.5 wt% to 10 wt%, 10 wt% to 20 wt%, 10 wt% to 15 wt%, 10 wt% to 12 wt% NaNO3, or any and all subranges formed by any of these endpoints.
[0167] In various embodiments, the ion exchange medium comprises from about 80 wt % to less than 100 wt % KNO 3 , based on the total amount of NaNO 3 and KNO 3 in the ion exchange medium. For example, the ion exchange medium of various embodiments may contain 80 wt % to 99.9 wt %, 80 wt % to 97.5 wt %, 80 wt % to 95 wt %, 80 wt % to 92.5 wt %, 80 wt % to 90 wt %, 90 wt % to 99.9 wt %, 90 wt % to 97.5 wt %, 90 wt % to 95 wt %, 90 wt % to 92.5 wt %, 92.5 wt % to 99.9 wt %, 92.5 wt % to 97.5 wt %, 92.5 wt % to 95 wt %, 95 wt % to 99.9 wt %, 95 wt % to 97.5 wt %, 97.5 wt % to 99.9 wt % KNO , based on the total amount of NaNO and KNO in the ion exchange medium, or any and all subranges formed by any of these endpoints.
[0168] According to various embodiments, the ion exchange medium further comprises 0.01 wt % to 0.5 wt % LiNO3, based on the total weight of the salt in the ion exchange medium. For example, the ion exchange medium of various embodiments may comprise 0.01 wt % to 0.5 wt %, 0.01 wt % to 0.3 wt %, 0.01 wt % to 0.1 wt %, 0.1 wt % to 0.5 wt %, 0.1 wt % to 0.3 wt %, 0.3 to 0.5 wt % LiNO3, or any and all subranges formed by any of these endpoints. In some specific embodiments, the ion exchange medium comprises 0.1 wt %, 0.09 wt %, 0.08 wt %, 0.07 wt %, or 0.06 wt % LiNO3, based on the total weight of the salt in the ion exchange medium.
[0169] The ion exchange treatment can be a single-step treatment or a multi-step treatment, for example, a two-step or three-step treatment. In an embodiment in which the ion exchange treatment includes multiple steps, it is understood that each step includes applying an ion exchange medium to the glass-ceramic article, and the ion exchange medium of each step can be different from the ion exchange medium of one or more other steps. However, each ion exchange medium contains greater than 0 wt % NaNO based on the total amount of NaNO3 and KNO3 in the ion exchange medium and less than or equal to about 20 wt % NaNO3, about 80 wt % to less than 100 wt % KNO3 based on the total amount of NaNO3 and KNO3 in the ion exchange medium, and 0.01 wt % to 0.5 wt % LiNO3 based on the total weight of the salt in the ion exchange medium.
[0170] In various embodiments, the temperature of the molten salt bath may be from about 380°C to about 550°C, and the immersion time may be from about 2 hours to about 16 hours.
[0171] Streak-free ion exchange treatment
[0172] In various embodiments, the ion exchange treatment uses a lower potassium concentration than is effective to produce a surface waveguide for FSM measurement, referred to herein as a "striation-free IOX". In these embodiments, the potassium, sodium, and lithium concentrations in the ion exchange medium are suitable for limiting the average sodium oxide contained in a depth of 100 nm from the surface to the glass-ceramic article to less than 10 mol% sodium oxide, as measured using glow discharge optical emission spectroscopy (GDOES). Despite the lack of surface waveguides, in various embodiments, the surface layer is chemically durable, making it particularly suitable for cover glass applications.
[0173] In various embodiments, the streak-free IOX treatment includes applying an ion exchange medium to one or more surfaces of the glass-ceramic article. The ion exchange medium may be a solution, a paste, a gel, or another suitable medium comprising KNO3, NaNO3, and LiNO3.
[0174] In various embodiments, the ion exchange medium comprises greater than 20 wt % NaNO and less than or equal to about 50 wt % NaNO, based on the total amount of NaNO and KNO in the ion exchange medium. For example, the ion exchange medium of various embodiments may comprise 20 wt % to 50 wt %, 20 wt % to 45 wt %, 20 wt % to 40 wt %, 20 wt % to 35 wt %, 20 wt % to 30 wt %, 30 wt % to 50 wt %, 30 wt % to 45 wt %, 30 wt % to 40 wt %, 30 wt % to 35 wt %, 35 wt % to 50 wt %, 35 wt % to 45 wt %, 35 wt % to 40 wt %, 40 wt % to 50 wt %, 40 wt % to 45 wt %, 45 wt % to 50 wt %, or any and all subranges formed by any of these endpoints, based on the total amount of NaNO and KNO in the ion exchange medium. It should be understood, however, that in some embodiments, NaNO 3 may be included in an amount greater than 50 wt %, but in such cases, depending on the specific amount of NaNO 3 and the temperature of the ion exchange treatment, an amount of LiNO 3 greater than about 0.15 wt % may be beneficial.
[0175] In various embodiments, the ion exchange medium comprises from about 50 wt % to about 80 wt % KNO, based on the total amount of NaNO and KNO in the ion exchange medium. For example, the ion exchange medium of various embodiments may comprise from 50 wt % to 80 wt %, from 50 wt % to 70 wt %, from 50 wt % to 65 wt %, from 50 wt % to 60 wt %, from 50 wt % to 55 wt %, from 55 wt % to 80 wt %, from 55 wt % to 70 wt %, from 55 wt % to 65 wt %, from 55 wt % to 60 wt %, from 60 wt % to 80 wt %, from 60 wt % to 70 wt %, from 60 wt % to 65 wt %, from 65 wt % to 80 wt %, from 65 wt % to 70 wt %, from 70 wt % to 80 wt % KNO, based on the total amount of NaNO and KNO in the ion exchange medium, or any and all subranges formed by any of these endpoints.
[0176] According to various embodiments, the ion exchange medium further comprises 0.04 wt % to 0.5 wt % LiNO3, based on the total weight of the salt in the ion exchange medium. For example, the ion exchange medium of various embodiments may comprise 0.04 wt % to 0.5 wt %, 0.04 wt % to 0.3 wt %, 0.04 wt % to 0.1 wt %, 0.1 wt % to 0.5 wt %, 0.1 wt % to 0.3 wt %, 0.3 to 0.5 wt % LiNO3, or any and all subranges formed by any of these endpoints, based on the total weight of the salt in the ion exchange medium. In some specific embodiments, the ion exchange medium comprises 0.1 wt %, 0.09 wt %, 0.08 wt %, 0.07 wt %, or 0.06 wt % LiNO3, based on the total weight of the salt in the ion exchange medium.
[0177] The ion exchange treatment can be a single-step treatment or a multi-step treatment, for example, a two-step or three-step treatment. In an embodiment in which the ion exchange treatment includes multiple steps, it is understood that each step includes applying an ion exchange medium to the glass-ceramic article, and the ion exchange medium of each step can be different from the ion exchange medium of one or more other steps. However, each ion exchange medium contains greater than 20% by weight of NaNO based on the total amount of NaNO and KNO in the ion exchange medium and less than or equal to about 50% by weight of NaNO, about 50% by weight to about 80% by weight of KNO based on the total amount of NaNO and KNO in the ion exchange medium, and 0.04% by weight to 0.5% by weight of LiNO based on the total weight of the salt in the ion exchange medium.
[0178] In various embodiments, the temperature of the molten salt bath may be from about 380°C to about 550°C, and the immersion time may be from about 2 hours to about 16 hours.
[0179] Without being bound by theory, it is believed that in glass-ceramics formed from lithium disilicate and / or petalite families, when the concentration of NaNO3 in the ion exchange process exceeds about 20 wt%, the increase in refractive index due to potassium ion exchange is suppressed by the decrease in refractive index due to sodium exchange for lithium ions. Therefore, during the streak-free ion exchange process, potassium streaks that are conventionally suitable for FSM metrology measurement are not generated. For example, Figure 5 As shown, it provides a 365 nm FSM spectrum of a glass of composition A ion-exchanged in 60 wt % KNO3 and 40 wt % NaNO3 and 0.1 wt % LiNO3. By comparison Figure 5 and Figure 2A, we can see that Figure 5 The fuzzy low-refractive-index fringes seen in Figure 2A, which indicate the ion exchange of sodium with lithium in the crystalline phase, do not appear in Figure 2. Therefore, FSM metrology may not be suitable for monitoring the progress of sodium ion exchange in the streak-free IOX treatment.
[0180] However, the surface compressive stress can be obtained from the birefringence using the FSM spectrum. For example, the compression depth and central tension were obtained using an Orihara SLP 2000 scattered light photoelastic stress meter operating at 405 nm, and the results are shown in Figure 6 For transparent glass-ceramics, a 405 nm wavelength may be particularly advantageous because it is believed that the 405 nm wavelength minimizes speckle. However, higher wavelengths (e.g., 633 nm) may also be used, but they may significantly increase speckle. In some such embodiments, speckle may be averaged by moving the sample during the measurement.
[0181] The Orihara SLP 2000 includes a built-in 2x telecentric lens that enables the camera to have a field of view of up to 600 μm in depth. However, due to the high refractive index nature of glass-ceramics, the depth perception extends to approximately 800 μm, making it possible to use the SLP 2000 to obtain complete stress profile measurements for the various glass-ceramic articles described herein.
[0182] In operation, a 405 nm laser diode is periodically phase modulated by a liquid crystal variable retarder before entering the glass ceramic. Due to the stress distribution in the glass ceramic, the scattered light undergoes changes in intensity and phase as it travels through the thickness of the glass ceramic. A camera set at 45° relative to the surface of the glass ceramic captures the vertical component of the intensity fluctuations along the laser path as the light is scattered in all directions. The phase shift experienced at each point along the laser path is captured by image analysis, and the internal stress σ can be inferred according to the following equation (2):
[0183]
[0184] Where λ is the wavelength of the laser, β is the stress optical coefficient (SOC), is the phase shift, and x is the optical path length.
[0185] The SLP 2000 software provides a real-time display of the laser beam inside the sample. In various embodiments, a sixth-order polynomial fit can be used to provide consistent results on various glass-ceramic samples. However, the processing area, laser wavelength, and appropriate fitting function can be changed according to the specific embodiment.
[0186] Alternatively, a quality control metric can be derived from the integral of the compressive stress. Specifically, the integral of the compressive stress from ion exchange is related to the number of ions that were ion exchanged. As larger ions replace smaller ions, the glass article undergoes dimensional growth, which is related to the central tension, as long as the ion exchange process is conducted below the peak central tension. Once the peak central tension is reached, although there is still growth from ion exchange, the correlation between dimensional growth and central tension is no longer valid. Figure 7 An example of the correlation of % size growth with central tension from three different salt concentrations is shown.
[0187] exist Figure 7 In , the central tension (in MPa) is shown along the X-axis, while the dimensional growth in length (in %) is shown along the Y-axis. Each glass ceramic sample is made of composition A. Curve 702 shows the correlation of the glass ceramic sample that was ion exchanged in a bath with 50 wt% KNO3, 50 wt% NaNO3 and 0.1 wt% LiNO3 at 470°C. Curve 704 shows the correlation of the glass ceramic sample that was ion exchanged in a bath with 70 wt% KNO3, 30 wt% NaNO3 and 0.1 wt% LiNO3 at 470°C. Curve 706 shows the correlation of the glass ceramic sample that was ion exchanged in a bath with 60 wt% KNO3, 40 wt% NaNO3 and 0.1 wt% LiNO3 at 500°C. As Figure 7 As shown, the % dimensional growth from ion exchange can be used as a measure of compressive stress below the peak compressive stress value. Specifically, curve 706 shows that after 8 hours, the central tension reaches about 95 MPa, and the increased ion exchange shows an increase in dimensional growth that is not related to the compressive stress. Specifically, for transparent glass and glass ceramic materials, the dimensional growth can be related to the central tension according to the following equation (3):
[0188] CT=1182*DG+20 (3)
[0189] Where CT is the core tension (in MPa) and DG is the dimensional growth in length in % when the core tension is below the peak core tension.
[0190] For opaque materials, the % size growth can be calibrated with the elemental distribution obtained by the microprobe and converted to stress using the lattice dilation constant according to the following equation (4):
[0191]
[0192] where C(z) is the concentration of large cations at z, h is the glass thickness, B is the network expansion coefficient, E is Young's modulus, v is Poisson's ratio, and z is the distance from the glass surface in the glass thickness, where it is 0 and h.
[0193] Ion exchange glass ceramic products
[0194] In various embodiments, the resulting ion exchange glass ceramic article can be transparent or opaque, and the depth of compression (DOC) is about 0.18t to about 0.25t from the outer surface of the ion exchange glass ceramic article, where t is the thickness of the ion exchange glass ceramic article. In other words, the stress in the ion exchange glass ceramic article changes from compressive stress to tensile stress at a depth of about 0.18t to about 0.25t from the outer surface of the ion exchange glass ceramic article. In various embodiments, the DOC may be greater than 80μm. For example, the compression depth may be 80μm to 300μm, 100μm to 250μm, 150μm to 200μm, or any and all sub-ranges formed by any of these endpoints. Deep DOC can provide damage resistance, for example, can provide resistance to sharp flaws, which can be caused by falling of the glass ceramic article on a rough surface (e.g., asphalt).
[0195] In various embodiments described herein, the maximum compressive stress (absolute value) at the outer surface of the obtained ion-exchanged glass-ceramic article is 1.8 to 2.2 times the maximum central tension (absolute value) (CT) of the ion-exchanged glass-ceramic article. For example, the absolute value of the maximum compressive stress can be, for example, 2|CT|. In an embodiment, the absolute value of the maximum central tension is at least 60 MPa or greater, or 70 MPa or greater. For example, the absolute value of the maximum central tension may be 60 MPa to 160 MPa, 60 MPa to 150 MPa, 60 MPa to 140 MPa, 60 MPa to 130 MPa, 60 MPa to 120 MPa, 60 MPa to 110 MPa, 60 MPa to 100 MPa, 70 MPa to 160 MPa, 70 MPa to 150 MPa, 70 MPa to 140 MPa, 70 MPa to 130 MPa, 70 MPa to 120 MPa, 70 MPa to 110 MPa, 70 MPa to 100 MPa, 80 MPa to 160 MPa, 80 MPa to 150 MPa, 80 MPa to 140 MPa, 80 MPa to 130 MPa, MPa, 80 MPa to 120 MPa, 80 MPa to 110 MPa, 80 MPa to 100 MPa, 90 MPa to 160 MPa, 90 MPa to 150 MPa, 90 MPa to 140 MPa, 90 MPa to 130 MPa, 90 MPa to 120 MPa, 90 MPa to 110 MPa, 90 MPa to 100 MPa, 100 MPa to 160 MPa, 100 MPa to 150 MPa, 100 MPa to 140 MPa, 100 MPa to 130 MPa, 100 MPa to 120 MPa, 100 MPa to 110 MPa, or any and all subranges formed by any of these endpoints.
[0196] In various embodiments, the ion exchange glass-ceramic article also has a maximum compressive stress of 108 MPa to 350 MPa. For example, the absolute value of the maximum compressive stress may be 108 MPa to 350 MPa, 108 MPa to 325 MPa, 108 MPa to 300 MPa, 108 MPa to 275 MPa, 108 MPa to 250 MPa, 108 MPa to 225 MPa, 108 MPa to 200 MPa, 180 MPa to 350 MPa, 180 MPa to 325 MPa, 180 MPa to 300 MPa, 180 MPa to 275 MPa, 180 MPa to 250 MPa, 180 MPa to 225 MPa, 180 MPa to 200 MPa, 200 MPa to 350 MPa, 200 MPa to 325 MPa, 200 MPa to 300 MPa, 200 MPa to 275 MPa. MPa, 300 MPa to 350 MPa, 300 MPa to 325 MPa, 325 MPa to 350 MPa, or any and all subranges formed by any of these endpoints.
[0197] Fracture toughness can also be used to characterize the ion-exchanged glass-ceramic article. In various embodiments, the ion-exchanged glass-ceramic article has a fracture toughness of 1 MPa√m or greater, as measured by the double cantilever beam method on a sample having the same composition but not ion-exchanged. For example, in various embodiments, the ion-exchanged glass-ceramic article has a fracture toughness of 1 MPa√m to 1.5 MPa√m, as measured by the double cantilever beam method.
[0198] The various embodiments described herein can also be used to reduce the fragility of glass ceramic products. Therefore, in various embodiments, after ion exchange, the glass ceramic product is not fragile. Fragile properties refer to the specific fracture behavior of glass ceramic products when they are impacted or damaged. As used herein, when the glass exhibits one or more of the following in the test area due to the fragility test, the glass is considered to be non-fragile: (1) four or fewer fragments with a maximum size of 1 mm or more, and / or (2) the number of bifurcations is less than or equal to the number of crack branches. Fragments, bifurcations, and crack branches are calculated based on any 2-inch × 2-inch square centered on the impact point. Therefore, for any 2-inch × 2-inch square centered on the impact point, if the glass meets one or both of the tests (1) and (2), the glass is considered to be non-fragile, and the impact point is the place where the fracture is produced according to the following procedure. In the fragility test, the impact probe is brought into contact with the glass, and the depth to which the impact probe extends into the glass increases in continuous contact repetitions. The gradually increasing depth of the impact probe allows the flaws generated by the impact probe to reach the tension zone while preventing the application of excessive external forces, which would hinder the accurate determination of the fragility of the glass. In some embodiments, the depth of the impact probe in the glass can be increased by about 5 μm for each repeated contact, wherein the impact probe does not contact the glass between each repeated contact. The test area is any 2-inch × 2-inch square centered on the impact point. As used herein, crack branches originate from the impact point, and if any part of the fragment extends into the test area, the fragment is considered to be within the test area. Although coatings, adhesive layers, etc. can be used in conjunction with the strengthened glass products described herein, these external constraints are not used to determine the fragility or fragility properties of glass-ceramic products. In some embodiments, a film that does not affect the fracture properties of the glass-ceramic product can be applied to the glass-ceramic product before the fragility test to prevent fragments from being ejected from the glass product, thereby improving the safety of the personnel performing the test.
[0199] In contrast, a brittle glass article does not exhibit four or fewer fragments or a number of forks that is less than or equal to the number of crack branches. In the fragility test described herein, the impact is delivered to the surface of the glass article with a force just sufficient to release the internal stored energy present in the strengthened glass article. That is, the point impact force is sufficient to generate one or more new cracks in the surface of the strengthened glass sheet and cause the crack to extend through the compression zone (i.e., to the compression depth) and into the tension zone (i.e., the region under central tension).
[0200] Thus, the chemically strengthened glass-ceramic articles described herein are "non-brittle" - that is, they do not exhibit the brittle properties described above when impacted by a sharp object.
[0201] Example
[0202] In order to more easily understand the various embodiments, reference is made to the following examples, which are intended to illustrate the various embodiments. Unless otherwise specified, the thickness of each sample in each example is 0.8 mm.
[0203] Example 1
[0204] Glass-ceramic samples formed from composition A were subjected to different ion exchange treatments and FSM spectra of each sample were obtained using a 365 nm Orihara FSM. The results are shown in Figures 8A-8E .
[0205] exist Fig. 8A In the present invention, the glass ceramic samples were subjected to an ion exchange treatment at 500° C. for 10 hours in a bath having 100 wt % KNO 3 and 0.1 wt % LiNO 3 . Figure 8B In the present invention, the glass ceramic samples were subjected to an ion exchange treatment at 500° C. for 12 hours in a bath having 95 wt % KNO 3 , 5 wt % NaNO 3 and 0.1 wt % LiNO 3 . Figure 8C In the present invention, the glass ceramic samples were subjected to an ion exchange treatment at 500° C. for 12 hours in a bath having 90 wt % KNO 3 , 10 wt % NaNO 3 and 0.1 wt % LiNO 3 . Figures 8A-8C As shown, TE and TM fringes suitable for ion exchange quality control metrology are produced.
[0206] exist Fig.8D In the present invention, the glass ceramic samples were subjected to an ion exchange treatment at 500° C. for 16 hours in a bath having 80 wt % KNO 3 , 20 wt % NaNO 3 and 0.1 wt % LiNO 3 . Fig. 8E In the present invention, the glass ceramic samples were subjected to an ion exchange treatment at 480° C. for 16 hours in a bath containing 80 wt % KNO 3 , 20 wt % NaNO 3 and 0.1 wt % LiNO 3 . Fig.8D and 8E The fringes in may be suitable for metrology using advanced image processing methods, but the contrast or critical angle shift of the fringes decreases due to increased sodium ion exchange, which reduces the refractive index. Without being bound by theory, as in Fig.8D and 8E As seen in Figure 3, the potassium streaks begin to fade when the sodium concentration exceeds about 10 wt% NaNO3 because the ion exchange of sodium for lithium occurs at a fast rate and reduces the refractive index of the surface layer more rapidly than the ion exchange of potassium for sodium can increase the refractive index. Fig.8D The samples in the experiment were also subjected to a longer treatment time (16 h) to obtain the same Figure 8CThe spectra shown are comparable to those shown.
[0207] Also measured for Figures 8A-8C The compressive stress and maximum central tension of each sample are Figures 8A-8C The corresponding graph is shown. Fig. 8A As shown, compared with the maximum central tension of glass ceramic products treated with KNO3 / NaNO3 / LiNO3 ( Figure 8B and 8C 71MPa and 84MPa respectively), the maximum central tension of the glass ceramics treated with pure KNO3 / LiNO3 salt bath is low (27MPa). However, the extended treatment time of the sample (containing 20 wt% NaNO3) Fig.8D and 8E ) resulted in a deep sodium profile that extended beyond the peak central tension and resulted in lower compressive stress values.
[0208] Example 2
[0209] Prior to ion exchange strengthening, the concentrations of the various constituent components of the glass network of the glass-ceramic article (e.g., glass formers, such as SiO2 and B2O3, intermediates, such as Al2O3, modifiers, such as CaO, Na2O, etc.) are substantially uniformly distributed from the outer surface of the glass-ceramic article through the thickness of the glass-ceramic article. For example, the glass-ceramic article includes one or more glass formers, and the concentration of the glass formers is substantially constant throughout the thickness of the glass-ceramic article. In addition, the glass-ceramic article includes one or more modifiers, such as Na2O and / or another alkali metal oxide, and the concentration of the modifiers is substantially constant throughout the thickness of the glass-ceramic article.
[0210] However, after ion exchange, the concentration of alkali metal oxides (e.g., K2O) in the glass ceramic article varies depending on the depth from the outer surface of the glass ceramic article. In order to determine the effect of single-stripe ion exchange treatment on glass ceramic articles, a glass ceramic article formed from composition A and having a thickness of 0.8 mm was subjected to single-stripe ion exchange treatment at 500° C. in a bath containing 80 wt. % KNO3, 20 wt. % NaNO3, and 0.1 wt. % LiNO3 for 16 hours (single-stripe example). At 470° C., another glass ceramic article formed from composition A and having a thickness of 0.8 mm was subjected to conventional ion exchange treatment for 12 hours in a bath containing 30 wt. % KNO3, 70 wt. % NaNO3, and 0.05 wt. % LiNO3, and then treated for 1 hour at 470° C. in a bath containing 30 wt. % KNO3 and 70 wt. % NaNO3 (conventional IOX example). The concentration distribution of various constituent components in the glass, such as alkali metal constituent components, was measured by electron probe microanalysis (EPMA), and the distribution curve is shown in FIG. Fig. 9 .
[0211] Specifically, for both the single stripe (902) and the conventional IOX treatment (904), the concentration of K2O decreases from the surface of the glass-ceramic article to a concentration of 0 mol% in the direction of the centerline CL of the glass-ceramic article.
[0212] The concentration of Na2O (906) increases first from the surface of the glass-ceramic article in the direction of the center line CL of the glass-ceramic article subjected to the single stripe 10X, and then decreases. That is, the Na2O concentration 904 in the glass-ceramic article that changes according to the distance from the surface initially has a positive slope, but then has a negative slope. In various embodiments, the difference between the surface Na2O concentration and the minimum Na2O concentration is less than 5 mol%, and the surface Na2O concentration is less than 10 mol%. In various embodiments, the concentration of Na2O is greater than 0 mol% throughout the thickness of the ion-exchanged glass-ceramic article. For example, in various embodiments, the concentration of Na2O is greater than 0 mol% and less than 2.5 mol%.
[0213] In contrast, the NaO concentration (908) of the glass ceramic article subjected to conventional IOX treatment has a surface peak that drops and decreases from the surface of the glass ceramic article in the direction of the centerline CL of the glass ceramic article. Thus, as can be seen by comparing 906 and 908, the single-stripe IOX treatment significantly reduces the amount of sodium near the surface (about 2.5 mol% vs. about 20 mol%), but the deep sodium distribution (which contributes to damage resistance) beyond about 80 μm is comparable to that of the conventional IOX treatment, indicating a deep compression depth.
[0214] In addition, Fig. 9In the embodiment, the Li2O concentration (910) of the glass-ceramic article subjected to single-striped IOX increases from the surface Li2O concentration to the maximum Li2O concentration at the center line CL as the distance increases from the surface of the glass-ceramic article to the center line CL of the glass-ceramic article. In various embodiments, the difference between the surface Li2O concentration and the maximum Li2O concentration is less than 5 mol%. In various embodiments, the maximum concentration of Li2O is 19 mol% to 32 mol%. In contrast, the Li2O concentration (912) of the glass-ceramic article subjected to conventional IOX increases sharply near the surface, and then from the surface of the glass-ceramic article to the center line CL of the glass-ceramic article, as the distance increases, the Li2O concentration continues to increase from the surface Li2O concentration to the maximum Li2O concentration at the center line CL. However, the difference between the surface Li2O concentration and the maximum Li2O concentration is greater than 10 mol%, greater than 15 mol%, or even greater than 18 mol%.
[0215] Although the concentration of alkali metal oxides in the glass-ceramic article changes due to ion exchange strengthening, it is understood that the concentration of other components of the glass network [e.g., glass formers, intermediate materials, and non-mobile modifiers such as alkaline earth metal oxides (CaO, MgO, etc.)] remains substantially constant (e.g., substantially uniform through the thickness of the glass-ceramic article).
[0216] Example 3
[0217] In order to further increase the center tension of glass-ceramic articles treated with single-stripe IOX, a two-step ion exchange process was developed. The articles in Example 3 were all formed from Composition A. Figures 10A-10H The FSM spectrum of a glass ceramic product subjected to single-stripe IOX treatment is shown. Specifically, Figures 10A-10H Each shows a 365 nm FSM spectrum of a glass-ceramic article formed from composition A and subjected to ion exchange treatment.
[0218] exist Fig. 10A In the present invention, the glass ceramic article was subjected to a treatment containing 90 wt % KNO3, 10 wt % NaNO3 and 0.1 wt % LiNO3 at 500°C for 12 hours. The resulting glass ceramic article had a maximum central tension of 84 MPa. The glass ceramic article was then subjected to a treatment containing 60 wt % KNO3, 40 wt % NaNO3 and 0.1 wt % LiNO3 at 500°C for 4 hours. The resulting glass ceramic article had a maximum central tension of 103 MPa. As can be seen by comparison Fig. 10A and Fig. 10B As shown, the first step shows good formation of stripes ( Fig. 10A ), while the second step increases the ion exchange of sodium ions and increases the central tension (including the maximum central tension) ( Fig. 10B). However, after the second step, the fringes begin to lose contrast (or "fade") due to increased sodium ion exchange, which lowers the refractive index of the surface layer.
[0219] exist Fig. 10C In the present invention, the glass ceramic article was subjected to a treatment containing 95 wt% KNO3, 5 wt% NaNO3 and 0.1 wt% LiNO3 at 500°C for 12 hours. The obtained glass ceramic article had a maximum central tension of 71 MPa. The glass ceramic article was then subjected to a treatment containing 60 wt% KNO3, 40 wt% NaNO3 and 0.1 wt% LiNO3 at 500°C for 4 hours. The obtained glass ceramic article had a maximum central tension of 98 MPa. Fig. 10A and Fig. 10B Again, the first step shows well-formed stripes ( Fig. 10C ), while the second step increases the ion exchange of sodium ions and increases the central tension (including the maximum central tension) ( Fig. 10D ). Likewise, after the second step, the fringes begin to lose contrast (or "fade") due to increased sodium ion exchange, which lowers the refractive index of the surface layer.
[0220] exist Fig.10E In the present invention, the glass ceramic article is subjected to a treatment containing 60 wt % KNO3, 40 wt % NaNO3 and 0.1 wt % LiNO3 at 500°C for 7 hours. The obtained glass ceramic article has a maximum central tension of 100 MPa. The glass ceramic article is then subjected to a treatment containing 93 wt % KNO3, 7 wt % NaNO3 and 0.1 wt % LiNO3 at 500°C for 4 hours ( Fig.10F The resulting glass ceramic product has a maximum central tension of 95 MPa. The high concentration of sodium salt in the first step produces a compressive stress with a deep DOC ( Fig.10E ), while potassium streaks are formed during the second step ( Fig.10F ), which includes high concentrations of potassium salts.
[0221] exist Figure 10G In the present invention, the glass ceramic article is subjected to a treatment containing 60 wt% KNO3, 40 wt% NaNO3 and 0.1 wt% LiNO3 at 500°C for 6 hours. The obtained glass ceramic article has a maximum central tension of 103 MPa. The glass ceramic article is then subjected to a treatment containing 90 wt% KNO3, 10 wt% NaNO3 and 0.1 wt% LiNO3 at 500°C for 5 hours. The obtained glass ceramic article has a maximum central tension of 101 MPa. Fig.10E and 10F Similarly, the sodium salt concentration in the first step produces a compressive stress with a deep DOC ( Figure 10G), while potassium streaks are formed during the second step ( Fig. 10H ), which includes high concentrations of potassium salts.
[0222] Example 4
[0223] Glass and glass ceramic articles were subjected to one of various ion exchange treatments and damage resistance was measured. Table 2 below provides the ion exchange conditions, stress profile characteristics, and strength (fracture) test values. All samples had a thickness of 0.8 mm.
[0224] Sample A is a glass article having a nominal composition of 71 SiO2, 1.9 B2O3, 12.8 Al2O3, 2.4 Na2O, 8.2 Li2O, 2.9 MgO, 0.8 ZnO, 0.02 Fe2O3, 0.01 ZrO2, and 0.06 SnO2, and subjected to conventional IOX treatment. The fracture toughness of Sample A obtained by the double cantilever beam method is 0.84 MPa√m. Sample B is a glass article having a nominal composition of 58.4 SiO2, 6.1 B2O3, 17.8 Al2O3, 1.7 Na2O, 0.2 K2O, 10.7 Li2O, 4.4 MgO, 0.6 CaO, 0.02 Fe2O3, 0.01 ZrO2, and 0.08 SnO2, and subjected to conventional IOX treatment. The fracture toughness obtained by the double cantilever beam method of sample B is 0.95MPa√m. Sample C is a glass-ceramic product formed by composition A and subjected to conventional two-step IOX treatment. Sample D is a glass-ceramic product formed by composition A and subjected to single-stripe IOX treatment of various embodiments. Sample E is a glass-ceramic product formed by composition A and subjected to two-step single-stripe IOX treatment of various embodiments. Sample F is a glass-ceramic product formed by composition A and subjected to different two-step single-stripe IOX treatments of various embodiments. Sample G is a glass-ceramic product formed by composition A and subjected to different two-step single-stripe IOX treatments of various embodiments.
[0225] Table 2:
[0226]
[0227]
[0228] The strength reported as fracture in Table 2 is measured by applying a fracture stress that causes failure using a four-point bending test after introducing damage to the glass, and the damage is introduced by applying 1.3J of energy using 80 sandpaper impact via a slapper. The method is described in US20190072479A1. The test is performed using a device based on a dynamic impact test including a pendulum, the surface of which varies from flat to curved, wherein the glass ceramic product test sample is mounted to a pendulum and then used to contact the test sample with a roughened impact surface. The device is described in more detail in International Application Publication No. WO2017100646, which is incorporated herein by reference in its entirety. In order to test, the sample is loaded on a rack, then pulled back from the equilibrium position of the pendulum (to a position where 1.3J of energy will be applied to the sample to be tested), and released to cause a dynamic impact on the impact surface. The impact surface includes an abrasive sheet attached to the impact surface, which is in the form of sandpaper and has the number specified in the embodiment. Cut the sandpaper into 25 mm square pieces and straighten the sandpaper if the pieces bend during cutting.
[0229] The radius of curvature of the curved surface on the substrate is selected to provide a bending tensile force of 100 MPa when the substrate is bent about the curved surface, so that the tensile force is an externally applied tensile force due to stress of the bent substrate.
[0230] Example 5
[0231] Next, the glass ceramic articles formed from composition A were subjected to ion exchange treatment, and their stress distribution curves were measured using RNF. The results are shown in Fig.11. A glass ceramic article formed from composition A and treated with 60 wt % KNO3, 40 wt % NaNO3, and 0.1 wt % LiNO3 at 500°C for 10 hours, followed by a single stripe ion exchange treatment with 93 wt % KNO3, 7 wt % NaNO3, and 0.1 wt % LiNO3 at 500°C for 5 hours (same as sample G in Table 2) exhibits a stress distribution curve 1102. A glass ceramic article formed from composition A and treated with 60 wt % KNO3, 40 wt % NaNO3, and 0.1 wt % LiNO3 at 500°C for 7 hours, followed by a single stripe ion exchange treatment with 93 wt % KNO3, 7 wt % NaNO3, and 0.1 wt % LiNO3 at 500°C for 5 hours (same as sample F in Table 2) exhibits a stress distribution curve 1104. A glass ceramic article (same as sample C of Table 2) formed from composition A and subjected to conventional ion exchange treatment with a bath containing 30 wt % KNO3, 70 wt % NaNO3 and 0.05 wt % LiNO3 at 470°C for 12 hours followed by 30 wt % KNO3, 70 wt % NaNO3 at 470°C for 1.5 hours exhibits stress profile 1106. Fig.11 As shown, the stress in both distribution curves 1102 and 1104 decreases from compressive stress to tensile stress as the distance from the outer surface of the glass-ceramic article increases.
[0232] The stress distribution curve 1106 of the glass-ceramic article with a low refractive index layer has a high compressive stress (e.g., greater than 80 MPa) from the surface to a depth of 0.1t or greater, where t is the thickness of the glass-ceramic. However, stress distribution curves 1102 and 1104 have increased compressive stress at a depth exceeding 120 μm or 0.15t. Specifically, the increased compressive stress is the following compressive stress: greater than or equal to 40 MPa at a depth of 0.15t, greater than or equal to 30 MPa at a depth of 0.19t, and greater than or equal to 20 MPa at a depth of 0.19t. In addition, stress distribution curves 1102 and 1104 exhibit significantly higher compression depths, exceeding 0.20t, 0.21t, or 0.22t.
[0233] Stress distribution curves 1102 and 1104 also include an explicit knee stress CS k , which appears in the depth range after the spike. Without being bound by theory, it is believed that the knee stress is caused by the potassium concentration stabilizing to the same level as in the interior of the sample. CS k The value of is 100 to 150 MPa. It should be understood that CS k
[0043] Ranges may be from 100 MPa to 150 MPa, 100 MPa to 140 MPa, 100 MPa to 130 MPa, 100 MPa to 120 MPa, 100 MPa to 110 MPa, 110 MPa to 150 MPa, 110 MPa to 140 MPa, 110 MPa to 130 MPa, 110 MPa to 120 MPa, 120 MPa to 150 MPa, 120 MPa to 140 MPa, 120 MPa to 130 MPa, 130 MPa to 150 MPa, 130 MPa to 140 MPa, 140 MPa to 150 MPa, or any and all subranges formed by any of these endpoints. For example, in embodiments with slightly lower LiNO3 content (e.g., 0.09 wt%, 0.08 wt%, or 0.07 wt%) in the last ion exchange step, higher CS can be obtained without forming a low refractive index layer on the surface. k value.
[0234] In various embodiments, the CS is greater than 70 MPa, 80 MPa, or even 90 MPa. k The values may provide enhanced fracture resistance during a drop event on a moderately rough surface. Without being bound by theory, it is believed that during a drop from a height of 1 m or more onto a rough surface, tensile stresses of, for example, 70 MPa and 80 MPa may occur near the surface and at depths up to 30-40 μm. Accordingly, in various embodiments, the CS of the ion-exchanged glass-ceramic article may be 100% tantalum, ... k The value is greater than 70 MPa. In various embodiments, CS k The measurements were performed by birefringence measurement of the critical angle transition in prism coupled (FSM) spectroscopy, where the birefringence is related to the CS k Directly related.
[0235] like Fig.11 As shown, stress profiles 1102 and 1104 also show surface spikes of compressive stress. Without being bound by theory, it is believed that the surface spikes are due to the increased concentration of potassium ions rather than sodium ions. Specifically, in these samples, potassium penetration drops from about 5 μm to about 12 μm, which is related to the low potassium concentration and the single-fringe FSM spectrum for each polarization.
[0236] exist Fig.11The stress at the surface visible in the graph shown is not considered to be accurate because the resolution of the refractive near field (RNF) method is limited, which limits the accuracy of representing the peak when the stress changes greatly over a very small distance. Therefore, in various embodiments, prism coupling measurements are used to measure or estimate the surface stress as much as possible. When the low refractive index surface layer is avoided but the surface is rich in potassium ions, the average compressive stress in the peak region of the sample corresponding to the stress distribution curves 1102 and 1104 is 150MPa to about 300MPa, while the surface stress is about 200MPa to about 490MPa. The upper limit is determined by subjecting the sample to ion exchange for a significantly longer time to obtain a double-stripe spectrum, measuring the surface compressive stress using a conventional method of measuring surface compressive stress by double-stripe spectroscopy, and then correcting for the decrease in compressive stress that occurs due to the excessively long ion exchange time. Without being bound by theory, the surface compressive stress and the central tension (including the maximum central tension) are sensitive to the amount of LiNO3 in the bath, and the compressive stress decreases from 400-490 MPa when the LiNO3 concentration is 0.05 wt% to 0.07 wt% to 350-450 MPa when the LiNO3 concentration is 0.07 wt% to 0.12 wt%, and decreases to 250-400 MPa at higher LiNO3 concentrations. It should be understood that the specific compressive stress value varies within a range depending on the Na / K ratio in the bath, where the highest value is obtained for a bath with a low concentration of NaNO3 (e.g., <5 wt%) and a high concentration of KNO3 (e.g., >95 wt%) in the final ion exchange step.
[0237] Additionally, stress profiles 1102 and 1104 have very small second order derivatives in the region between the bottom of the potassium-rich surface spike and a depth substantially exceeding the compression depth. This substantially linear region extends to depths greater than 0.25t to 0.4t. For example, Fig.11 As shown, the substantially linear region of the distribution curve exceeds 200 μm, even exceeding 240 μm, 280 μm, or even 320 μm. The starting point of the substantially linear region is less than 50 μm, and depending on the specific embodiment, it can be seen as low as 35 μm, 20 μm, 15 μm, or even 10 μm. In contrast, the stress distribution curve 1106 has an extremely high second-order derivative in the first 0.1t or 80 μm. The short word "substantially linear" means that the absolute value of the second-order derivative of the stress distribution curve in the area of interest does not exceed a limit proportional to the average slope of the area, where the limit is 10 inverse mm. In some embodiments, in order to obtain a better approximation of the linear distribution curve segment, the limit can be set to 9, 8, 7, 6 or 5 inverse mm.
[0238] In the depth range of 20 to 240 μm (0.025t to 0.3t), the average slope of the stress distribution curve 1102 is about 580 MPa / mm, while the second-order derivative remains at -3000 to 3000 MPa / mm. 2 Therefore, within the specified depth range, the ratio of the absolute value of the second-order derivative to the absolute value of the first-order derivative is less than 6. In the depth range of 40 to 200 μm (0.05t to 0.25t), the ratio is lower than 5.
[0239] In various embodiments, the second derivative in the region of interest is estimated by obtaining a close polynomial fit to the distribution curve in the region of interest and then taking the derivative of the polynomial fit. This approach can reduce or even eliminate the noise that is typically present when the second derivative of the experimental distribution curve is directly calculated by finite differences. However, in some embodiments, it may be difficult to obtain a close polynomial fit (e.g., R 2 999 of a polynomial fit). In such an embodiment, another aspect of a substantially linear segment may be considered, for example, the local slope does not vary significantly within the segment. For example, in the region of interest, the slope of the stress distribution curve 1102 is not less than 470 MPa / mm and does not exceed 640 MPa / mm, so the total change in slope less than 170 MPa / mm does not exceed 30% of the average slope of the region. Therefore, in some embodiments, "substantially linear" means that the total change in slope does not exceed 30%, 25%, 20%, or 15% of the average slope.
[0240] The average slope of stress distribution curve 1104 in the deep region of interest (excluding the peak region) is slightly higher than that of stress distribution curve 1102. Specifically, the average slope is 600 to 670 MPa / mm. Like stress distribution curve 1102, depending on the specific conditions for observing the basic linear distribution curve, the basic linear region of stress distribution curve 1104 extends from a lower limit of 30 μm, 25 μm, 20 μm or 15 μm to an upper limit of 320 μm, 300 μm, 280 μm, 240 μm or 200 μm. The upper limit represents most of the thickness (e.g., 0.25t, 0.3t, 0.35t, 0.37t or even 0.4t). Therefore, in various embodiments, the stress distribution curve of the ion exchange glass ceramic product has a basically linear region, which spans a range of 0.02t to 0.4t, and a width greater than 0.25t or 0.3t, even when the conditions for observing the basic linear distribution curve are the most stringent.
[0241] Stress distribution curves 1102 and 1104 also show a peak central tension (which is the maximum central tension in the illustrated embodiment) of 60 MPa to 120 MPa. In some embodiments, the peak central tension is less than 108 MPa or 102 MPa. Without being bound by theory, it is believed that peak central tension values of less than 120 MPa, or even 108 MPa, can reduce or eliminate the formation of a low refractive index surface layer and / or chemical durability issues. It is also believed that reducing the LiNO3 content from 0.1 wt. % to 0.09 wt. %, 0.08 wt. % or even 0.07 wt. % can increase the peak central tension. In addition, it is believed that higher central tension levels (including higher maximum central tensions) can be obtained by more carefully controlling the composition of the ion exchange bath, especially the LiNO3 content.
[0242] like Fig.11 As shown, stress profiles 1102 and 1004 also have depth integrals of compressive stresses of 9.9 to 12.5 MPa*mm in each compression region, and average stresses in the compression region are 52 MPa to 66 MPa. For both stress profiles 1102 and 1004, the total compressive stress integral in the two compression regions is 23.5 MPa to 31.3 MPa when divided by the 0.8 mm thickness. However, when the LiNO3 content of the ion exchange bath is reduced to 0.06-0.09 wt%, a slightly higher stress integral of up to 16 MPa*mm is possible, and a slightly lower stress integral of 8 MPa*mm is obtained due to the increase in the LiNO3 content of the bath caused by ion exchange of multiple components. Therefore, by changing the LiNO3 content of the bath, the average compressive stress in the compression region can be changed from 85 MPa (when the LiNO3 level is 0.06-0.08 wt%) to 45 MPa (when the LiNO3 level is 0.2 to 0.3 wt%). In various embodiments, the total compressive stress integral of the two compression regions (e.g., near each opposing surface of the glass-ceramic article) is 20 MPa to 40 MPa when divided by the thickness of the glass-ceramic article. It should be understood that due to the balance of forces between the compression region and the tension region, the same value and range of the thickness-normalized stress will apply to the thickness-normalized stress integral in the tension region.
[0243] Example 6
[0244] The glass ceramic articles were subjected to various streak-free ion exchange treatments, and their stress profiles were measured using RNF. Specifically, stress profile 1202 corresponds to a glass ceramic article formed from composition A and treated with 60 wt % KNO3, 40 wt % NaNO3, and 0.1 wt % LiNO3 at 500°C for 8 hours. Stress profile 1204 corresponds to a glass ceramic article formed from composition A and treated with 70 wt % KNO3, 30 wt % NaNO3, and 0.1 wt % LiNO3 at 470°C for 8 hours (sample O below). Stress profile 1206 corresponds to a glass ceramic article formed from composition A and treated with 70 wt % KNO3, 30 wt % NaNO3, and 0.1 wt % LiNO3 at 470°C for 13 hours (sample P below). Finally, stress distribution curve 1208 corresponds to a glass-ceramic article (same as sample C of Table 2) formed from composition A and treated with a conventional ion exchange treatment, wherein the conventional ion exchange treatment includes a first step of treating with 30 wt % KNO3, 70 wt % NaNO3 and 0.05 wt % LiNO3 at 470°C for 12 hours, and a second step of treating with 30 wt % KNO3 and 70 wt % NaNO3 at 470°C for 1.5 hours.
[0245] like Fig.12 As shown, each stress distribution curve includes a compression depth of about 20% of the thickness of the glass ceramic article (0.8 mm for each sample). The CS (z) of the stress distribution curve 1202 has a generally positive second-order derivative, but it also includes a substantially linear region extending from 50 μm to a depth of 240 μm (0.05t to 0.3t), or more strictly, from 56 μm to 208 μm (0.07t to 0.26t). The average stress slope in the substantially linear region is about 1000 MPa / mm, and the compression depth is about 0.17 mm (0.21t). The maximum central tension is 107 MPa. The stress distribution curve 1202 also has a high CS of 210 to 220 MPa. k , and the depth integral of the compressive stress in the compression region is equal to 16 MPa*mm. The tensile stress integral in the tension region is 32 MPa*mm, which balances the sum of the depth integrals of the compression regions on both sides of the tension region. The ratio of the total compressive stress integral to the thickness is 40 MPa. In addition, the average compressive stress in the compression region is 94 MPa, which is obtained by dividing the depth integral from z=0 to DOC (0.17 mm for the stress distribution curve 1202) at the surface by the depth range from 0 to DOC. This average compressive stress is substantially unchanged when the distribution curve is scaled with thickness (e.g., by shortening the ion exchange time which is proportional to the square of the thickness).
[0246] like Fig.12 As shown, stress distribution curve 1204 is also characterized by having a continuous positive second-order derivative in the entire compression region of the glass ceramic product and through most of the tensile regions on the inside. The compressive stress integral in each compression zone is 15.6MPa*mm. The total stress integral (due to stress balance, therefore any one of the compressive stress or tensile stress) divided by thickness (0.8mm) is 39MPa. The average compressive stress in the compression zone is 99.4MPa, and as mentioned above, when the distribution curve is scaled with thickness, it is substantially unchanged.
[0247] Stress profile 1204 has a generally higher second derivative absolute value, and a small portion (from about 80 μm to about 200 μm, or from 0.1t to 0.25t) is substantially linear. Stress profile 1204 also has slightly lower compressive stress at depths exceeding 60 μm, and higher compressive stress at depths below 50 μm, compared to stress profile 1202.
[0248] However, for the first 200 μm (or 0.25t), the function CS(z) of stress profiles 1202 and 1204 both have the highest second-order derivative, which occurs in the first 50 μm (or 0.06t). More specifically, excluding the potassium-rich region of the first 10 μm, the highest second-order derivative occurs between 12 μm and 40 μm depth. Compared to the highest second-order derivative of stress profile 1208, the highest second-order derivative of each of stress profiles 1202 and 1204 is significantly smaller (25,000 to 40,000 MPa / mm for stress profile 1202). 2 , and the stress distribution curve 1204 is 40,000 to 70,000 MPa / mm 2 ), the highest second-order derivative of stress profile 1208 in the first 50 μm is twice or more that of stress profile 1204. It should be understood that when the LiNO3 concentration in the final ion exchange step is less than 0.1 wt%, higher second-order derivatives, such as up to 100,000 MPa / mm 2 , and when the LiNO3 concentration is greater than 0.06 or 0.07 wt% and less than 0.1 wt%, the second-order derivative can be obtained without forming a low-refractive-index surface layer.
[0249] Stress profiles 1202 and 1204 may also be characterized by the range of slopes observed in the compression region. In various embodiments, the surface slope in the potassium-rich region at a depth of about 10 μm is not included. Specifically, the CS of stress profile 1202 is k1202 has a maximum central tension of 107 MPa, while stress profile 1204 has a significantly lower maximum central tension of 77 MPa.
[0250] Stress profiles 1202 and 1204 each exhibit simultaneously high compressive stress at a first depth of about 40 μm (0.05 t) and a second depth of 120 μm (0.15 t), wherein the compressive stress is greater than 100 MPa at the first depth and greater than 30 MPa at the second depth. Without being bound by theory, it is believed that this provides significant protection against higher stress events acting on shallow to medium depth flaws and lower to medium stress events acting on deep flaws.
[0251] The DOC of stress profile 1206 is 0.17 mm, and the depth integral of the compressive stress in each compression zone is equal to 14.4 MPa*mm. The average compressive stress in the compression zone is 84.7 MPa, and the total stress integral divided by the thickness (0.8 mm) is 36 MPa. Except for the potassium-rich surface layer, the stress profile 1206 has a thickness of 14.4 MPa*mm. Fig.11 1104, except for having a slightly smaller DOC. Specifically, similar to stress profiles 1102 and 1104, stress profile 1206 has an extended substantially linear region, indicating that the streak-free ion exchange process described herein can provide a similar stress profile and, therefore, similar fracture resistance, thereby eliminating the need to generate a single streak spike for quality control. In addition, stress profile 1206 has a significantly higher CS at about 170 MPa than stress profiles 1102 and 1104. k Thus, the average compressive stress in the compression region of stress profile 1206 is slightly higher than stress profiles 1102 and 1104 having higher DOCs.
[0252] Example 7
[0253] Glass and glass ceramic articles were subjected to one of various ion exchange treatments and damage resistance was measured. Table 3 below provides the ion exchange conditions, stress profile characteristics, and strength (fracture) test values.
[0254] Sample H is a glass product with the same properties as above-mentioned sample A and subjected to the same ion exchange conditions. Sample I is a glass product with the same properties as above-mentioned sample B and subjected to the same ion exchange conditions. Sample J is a glass-ceramic product (same as above-mentioned sample C) formed by composition A and subjected to conventional two-step 10X processing. Samples K, L and M are glass-ceramic products formed by composition A and subjected to the streak-free 10X processing of each embodiment of 4,8 or 12 hours respectively. Samples N, O, P and Q are glass-ceramic products formed by composition A and subjected to the different streak-free 10X processing of each embodiment of 4,8,13 or 16 hours respectively. Samples R, S and T are glass-ceramic products formed by composition A and subjected to the different streak-free 10X processing of each embodiment of 4,8 or 16 hours respectively.
[0255] Table 3:
[0256]
[0257]
[0258] The strength reported at break in Table 3 is measured by applying a fracture stress that causes failure using a four-point bending test after introducing damage to the glass, the damage being introduced via an applicator using 80 grit sandpaper impacting 1.3 J. The method is described in US20190072479A1. The fracture strength of samples J, K, L, and M is plotted in Fig.13 Samples J to T (made from composition A) all do not form a low refractive index layer that is easily degraded, but are still significantly better than Comparative Examples H and I, despite not forming a low refractive index layer. Compared to the glass examples of samples H and I, these samples (J to T) that resist surface degradation show mechanical properties closer to the strength of the glass-ceramic double ion exchange sample (sample J).
[0259] Example 8
[0260] Glass and glass ceramic articles were subjected to one of various ion exchange treatments and damage resistance was measured using a drop test. The results are shown in Figures 14A-14C. The glass-based product of Example U-BB is mounted on the same tray assembly, wherein the size, shape, and weight of the tray are adjusted to simulate a cell phone assembly. As used herein, the term "glass-based" means any material comprising at least a portion of glass, including glass and glass-ceramics. The tray is dropped onto 180 grit sandpaper in a horizontal orientation at incremental heights starting from 20 cm, with the glass-based material facing downward - a flat drop. If the glass-based product survives a drop from a certain height (e.g., 20 cm), the tray is dropped again from a greater height (e.g., 30 cm, 40 cm, 50 cm, etc.) in 10 cm increments, up to a height of 225 cm. The intact glass-based product is dropped onto 80 grit sandpaper (in the same cell phone assembly). Figures 14A-14C The height at which the glass-based article failed on both 180-grit and 80-grit sandpaper is plotted.
[0261] Fig.14A The results of incremental flat drops on 80 grit sandpaper for Samples U, V, W, and X are shown. Sample U is a glass article formed from a nominal composition having, in mole %: 63.6SiO2; 2.3B2O3; 15Al2O3; 9.3Na2O; 5.9Li2O; 1.2ZnO; .05SnO2, 2.53P2O5. The fracture toughness obtained by the double cantilever beam method for Sample U is 0..76MPa√m. Sample V is a glass article formed from a nominal composition having, in mole %: 71SiO2; 1.9B2O3; 12.8Al2O3; 2.4Na2O; 8.2Li2O; 2.9MgO; 0.8ZnO; 0.02Fe2O3; 0.01ZrO2; 0.06SnO2. The fracture toughness of sample V obtained by the double cantilever method was 0.84 MPa√m. Sample W was a glass article formed of the following nominal composition, wherein the nominal composition had, in mole %: 58.4 SiO2; 6.1 B2O3; 17.8 Al2O3; 1.7 Na2O; 0.2 K2O; 10.7 Li2O; 4.4 MgO; 0.6 CaO; 0.02 Fe2O3; 0.01 ZrO2; 0.08 SnO2. The fracture toughness of sample W obtained by the double cantilever method was 0.95 MPa√m. Sample X was a glass article formed of composition A. Samples U, V, W and X were each subjected to conventional ion exchange treatments including a first step of treatment at 380°C for 4 hours with a bath containing 70 wt % NaNO3 and 30 wt % KNO3, and a second step of treatment at 380°C for 40 minutes with a bath containing 7 wt % NaNO3 and 93 wt % KNO3.
[0262] Fig. 14B and 14CThe results of incremental flat drop of samples Y, Z, AA and BB on 180 grit and 80 grit sandpaper, respectively, are shown. Samples Y, Z, AA and BB were each formed from composition A. Sample Y was subjected to a conventional two-step ion exchange treatment, including a first step of treating with 70 wt% NaNO3, 30 wt% KNO3 and 0.05 wt% LiNO3 at 470°C for 12 hours, followed by treating with 70 wt% NaNO3 and 30 wt% KNO3 at 470°C for 1.5 hours (same as line 1106 and Example 4C, and a conventional process similar to Example 2). Sample Z was subjected to a two-step streak-free ion exchange treatment, including a first step of treating with 40 wt% NaNO3, 60 wt% KNO3 and 0.1 wt% LiNO3 at 500°C for 6 hours, followed by treating with 10 wt% NaNO3, 90 wt% KNO3 and 0.1 wt% LiNO3 at 500°C for 5 hours (similar to line 1104, Example 4F). Sample AA was subjected to a single-step streak-free ion exchange treatment at 500°C for 8 hours including 40 wt% NaNO3, 60 wt% KNO3, and 0.1 wt% LiNO3 (same as Example 7L). Sample BB was subjected to a single-step streak-free ion exchange treatment at 470°C for 8 hours including 30 wt% NaNO3, 70 wt% KNO3, and 0.1 wt% LiNO3 (same as Example 70 and line 1204).
[0263] like Figures 14A-14C As shown, except for the two glass-based articles of Examples U and V, all others were intact when dropped from a height of up to about 250 cm onto 80-grit sandpaper (providing an average intact drop height of 160 cm to 178 cm). Figures 14A-14C It is shown that the ion-exchanged glass-ceramic articles of various embodiments herein exhibit statistically equivalent drop performance to glass articles chemically strengthened according to prior art ion-exchange processes.
[0264] Example 9
[0265] To determine the effects of the streak-free ion exchange treatments of various embodiments on aging and corrosion, glass ceramic articles were prepared and subjected to one of the various ion exchange treatments. Each glass ceramic article was formed from composition A. Table 4 below shows the ion exchange treatment conditions and accelerated aging test results. To determine the accelerated aging results, the samples were placed in a chamber at 85°C and 85% relative humidity for a period of time (reported in Table 4) and examined for corrosion.
[0266] Table 4:
[0267]
[0268] As shown in Table 4, the streak-free IOX treatment described in various embodiments yielded significantly improved accelerated aging results.
[0269] To further investigate the effects of aging, optical micrographs of Sample CC were obtained before and after the sample was subjected to an accelerated aging test at 85°C and 85% relative humidity for 144 hours ( Fig.15A For the previous Fig. 15B For the later). We also obtained sample JJ at 48 hours ( Fig. 15C ) and 144 hours ( Fig.15D ), Sample JJ is a glass-ceramic article formed from Composition A and subjected to a streak-free ion exchange treatment comprising treatment with 90 wt % KNO3, 10 wt % NaNO3, and 0.1 wt % LiNO3 at 470°C for 12 hours. As can be seen in the optical micrographs, Sample CC exhibited severe corrosion at 144 hours, while Fig. 15C and 15D Sample JJ is shown with no visible corrosion.
[0270] Using SIMS depth profiling, elemental depth profiles were obtained for the first 300 nm of samples CC and JJ. These profiles are shown in Fig.16A and 16B .like Fig.16A As shown in Figure 2, sample CC formed a hydrated surface layer in which sodium was consumed and reacted with atmospheric CO2. Fig. 16B As shown, sample JJ did not form a hydration layer.
[0271] Through chemical strengthening, various embodiments described herein can obtain improved glass-ceramic properties, such as improved damage resistance, improved chemical durability, and reduced corrosion when exposed to high humidity conditions. In addition, the ion exchange treatment described herein can cause the formed glass-ceramic article to include a single stripe for FSM metrology quality control technology, or no stripe. Various embodiments described herein also provide additional or alternative quality control processes to be used when, for example, no stripe is obtained by the ion exchange treatment or when the glass-ceramic article is opaque.
[0272] The reinforced articles disclosed herein, such as ion-exchanged glass-ceramic articles, can be incorporated into another article, such as an article having a display (or display article) [e.g., consumer electronics, including mobile phones, tablets, computers, navigation systems, wearable devices (such as watches), etc.]; architectural articles; transportation articles (e.g., automobiles, trains, aircraft, ships, etc.), appliance articles, or any article requiring a certain degree of transparency, scratch resistance, abrasion resistance, or a combination of the above properties. Fig.18A and 18BExemplary articles comprising any of the reinforced articles disclosed herein are shown. Specifically, Fig.18A and 18B A consumer electronic device 1800 is shown, which includes a housing 1802 having a front surface 1804, a rear surface 1806, and side surfaces 1808; electrical components (not shown) at least partially or completely located within the housing and including at least a controller, storage, and a display 1810, the display being at or adjacent to the front surface of the housing; and a cover substrate 1812 at or above the front surface of the housing such that the cover substrate 1812 is above the display. In some embodiments, at least one of the cover substrate 1812 or a portion of the housing 102 can include any of the reinforcement articles disclosed herein.
[0273] It is obvious to those skilled in the art that various modifications and changes can be made to the embodiments described herein without departing from the spirit and scope of the subject matter claimed for protection. Therefore, this specification is intended to cover modifications and variations of the various embodiments described herein, as long as these modifications and variations fall within the scope of the attached claims and their equivalents.
Claims
1. An ion exchange glass ceramic article comprising a residual glass content of up to 30% and at least 70% of a crystalline phase, the crystalline phase being selected from lithium disilicate, petalite, β-quartz, β-spodumene solid solution, and combinations thereof; wherein the crystalline phase is composed of a main crystalline phase consisting of petalite, a main crystalline phase consisting of lithium disilicate, or a combination thereof, the ion exchange glass ceramic article having a thickness t and comprising stress, the stress decreasing as the distance from the outer surface of the ion exchange glass ceramic article toward the center line increases, wherein: The stress decreases according to a substantially linear function from a depth of about 0.07t to a depth of about 0.26t from an outer surface of the ion-exchanged glass-ceramic article; The stress changes from a compressive stress to a tensile stress at a depth of about 0.18t to about 0.25t from the outer surface of the ion-exchanged glass-ceramic article; and The maximum compressive stress at the outer surface of the ion-exchanged glass article is 200 MPa to 350 MPa, and the maximum central tension (CT) is greater than 60 MPa.
2. The ion exchange glass ceramic product according to claim 1, wherein: The fracture toughness of the ion-exchanged glass-ceramic article is 1 MPa√m to 1.5 MPa√m, as measured by a double cantilever beam method.
3. The ion exchange glass-ceramic product according to claim 1, wherein: The maximum compressive stress is 1.8 to 2.2 times the maximum central tension.
4. The ion exchange glass-ceramic product according to claim 1, wherein: The ion exchange glass-ceramic product has a Na2O concentration at the outer surface of less than 10 mol%.
Citation Information
Patent Citations
Corrosion indicator for use with a piping system, and a piping system using the corrosion indicator
US20190072479A1
Systems and methods for measuring a profile characteristic of a glass sample
US8854623B2
Fusion-formable glass-based articles including a metal oxide concentration gradient
WO2017100646A1
Double ion exchange process
CN105408272A
Crack-Resistant Glass-Ceramic Articles And Methods For Making The Same
CN105829256A